Ultraviolet curable resin composition, optical component, method for producing optical component, light emitting device and method for producing the same
By using an ultraviolet curable resin composition containing a photopolymerizable compound and a photopolymerization initiator, and controlling the irradiation conditions of the ultraviolet rays, the problem of stripe-like concave and convexity on the surface of the cured product is solved, and the luminescence characteristics of the light emitting device are improved.
Patent Information
- Application Number
- CN202111147228.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-09-28
AI Technical Summary
When the cured product is made by ultraviolet curing, stripe-like concave and convexity are easily formed on the surface of the cured product, which affects the luminescence characteristics of the light emitting device.
The ultraviolet curable resin composition containing a photopolymerizable compound and a photopolymerization initiator is used to control the difference in curing shrinkage rate by adjusting the irradiation intensity and accumulated light of the ultraviolet rays, and preventing the formation of striped concave and convexity.
It effectively prevents stripe-like concave and convexity on the surface of the cured substance, improves the luminous characteristics of the light emitting device, and ensures the optical performance of the optical components.
Smart Images

Figure CN114316650B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an ultraviolet curable resin composition, an optical component, a method for producing an optical component, a light-emitting device, and a method for producing a light-emitting device. Specifically, the present invention relates to an ultraviolet curable resin composition containing a photopolymerizable compound and a photopolymerization initiator, an optical component made from the ultraviolet curable resin composition, a method for producing an optical component using the ultraviolet curable resin composition, a light-emitting device having the optical component, and a method for producing a light-emitting device using the ultraviolet curable resin composition. Background Art
[0002] In a light emitting device having a light emitting element such as an organic EL element as a light source, for example, the organic EL element is arranged on a supporting substrate, a transparent substrate is arranged to face the supporting substrate, and a transparent sealing material is filled between the supporting substrate and the transparent substrate. The sealing material is produced by, for example, an inkjet method.
[0003] For example, International Publication No. 2018 / 074506 discloses a sealant for an organic EL display element, which is characterized in that it contains a polymerizable compound and a polymerization initiator, has a viscosity of 5 to 50 mPa·s at 25°C, a surface tension of 15 to 35 mN / m at 25°C, and a Poisson's ratio of a cured product at 25°C of 0.28 to 0.40 (see Claim 1 of International Publication No. 2018 / 074506). Summary of the invention
[0004] Problems to be solved by the invention
[0005] According to the inventor's research, when a cured product is produced by curing a UV-curable resin composition by irradiating UV rays, stripe-shaped concavities and convexities may be formed on the surface of the cured product. In particular, when the coating film of the UV-curable resin composition is cured by irradiating the surface of the coating film with UV rays from a light-emitting diode while moving the irradiation position, stripe-shaped concavities and convexities are easily generated. Such concavities and convexities may deteriorate the light-emitting characteristics of the light-emitting device.
[0006] The present invention aims to provide an ultraviolet curable resin composition which is unlikely to produce stripe-shaped unevenness on the surface of a cured product when the cured product is produced by irradiating ultraviolet rays, an optical component produced from the ultraviolet curable resin composition, a method for producing an optical component using the ultraviolet curable resin composition, a light-emitting device having the optical component, and a method for producing a light-emitting device using the ultraviolet curable resin composition.
[0007] Means for solving problems
[0008] The ultraviolet curable resin composition of one embodiment of the present invention contains a photopolymerizable compound (A) and a photopolymerization initiator (B). A coating film having a thickness of 10 μm is prepared from the ultraviolet curable resin composition and irradiated at an intensity of 7 W / cm 2 And the accumulated light intensity is 2.1J / cm 2 The curing shrinkage when the coating film is irradiated with ultraviolet light having a peak wavelength in a wavelength range of 385 nm to 405 nm under the conditions of irradiation intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 The absolute value of the difference in curing shrinkage when irradiated with the above-mentioned ultraviolet rays under the conditions of is less than 2 percentage points.
[0009] An optical component according to one embodiment of the present invention includes a cured product of the ultraviolet curable resin composition.
[0010] A method for producing an optical component according to one embodiment of the present invention includes: after molding the ultraviolet curable resin composition by an inkjet method, irradiating the ultraviolet curable resin composition with ultraviolet rays to cure the composition.
[0011] A light emitting device according to one embodiment of the present invention includes a light source and an optical component that transmits light emitted from the light source, wherein the optical component includes a cured product of the ultraviolet curable resin composition.
[0012] A method for manufacturing a light emitting device according to one embodiment of the present invention is a method for manufacturing a light emitting device including a light source and an optical component that transmits light emitted from the light source, and includes a step of manufacturing the optical component by the method for manufacturing the optical component.
[0013] Effects of the Invention
[0014] According to one embodiment of the present invention, there can be provided an ultraviolet curable resin composition which is not prone to producing stripe-like unevenness on the surface of a cured product when the cured product is produced by irradiating ultraviolet rays to cure the product, an optical component produced from the ultraviolet curable resin composition, a method for producing an optical component using the ultraviolet curable resin composition, a light-emitting device having the optical component, and a method for producing a light-emitting device using the ultraviolet curable resin composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic cross-sectional view showing a first example of a light emitting device according to an embodiment of the present invention. DETAILED DESCRIPTION
[0016] Hereinafter, one embodiment of the present invention will be described.
[0017] The ultraviolet curable resin composition of this embodiment (hereinafter, also referred to as composition (X)) contains a photopolymerizable compound (A) and a photopolymerization initiator (B). A coating film with a thickness of 10 μm is prepared from the composition (X) and irradiated at an intensity of 7 W / cm 2 And the accumulated light intensity is 2.1J / cm 2 The curing shrinkage ratio (hereinafter also referred to as the first curing shrinkage ratio) when the coating film is irradiated with ultraviolet light having a peak wavelength in the wavelength range of 385 nm to 405 nm under the conditions of irradiation intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 The absolute value of the difference in cure shrinkage rate (hereinafter also referred to as the second cure shrinkage rate) under the conditions of irradiation (hereinafter also referred to as the cure shrinkage rate difference) is less than 2 percentage points.
[0018] In the present embodiment, if the difference between the first cure shrinkage rate and the second cure shrinkage rate can be achieved to be 2 percentage points or less when using ultraviolet rays with a peak wavelength in a wavelength range of 385nm to 405nm, it is acceptable if the difference between the first cure shrinkage rate and the second cure shrinkage rate cannot be achieved to be 2 percentage points or less when using ultraviolet rays with a peak wavelength in other wavelengths in the above wavelength range. It is particularly preferred if the difference between the first cure shrinkage rate and the second cure shrinkage rate can be achieved to be 2 percentage points or less when using ultraviolet rays with a peak wavelength of 395nm. It is also preferred that the difference between the first cure shrinkage rate and the second cure shrinkage rate can be achieved to be 2 percentage points or less even when the peak wavelength of ultraviolet rays is any one of the wavelength ranges of 385nm to 405nm.
[0019] According to the present embodiment, when a cured product is produced by irradiating the composition (X) with ultraviolet rays, it is difficult to generate streaky concavoconvexities on the surface of the cured product. This is considered to be because the absolute value of the difference between the first cure shrinkage rate and the second cure shrinkage rate of the composition (X) is small, so that when the composition (X) is cured, it is difficult to generate local differences in the amount of shrinkage, that is, the composition (X) as a whole is easy to shrink uniformly.
[0020] In particular, when the surface of the coating of the ultraviolet curable resin composition is irradiated with ultraviolet light from a light emitting diode while the irradiation position of the ultraviolet light is moved to cure the coating, in the coating, it is easy to produce a relatively high portion of ultraviolet irradiation along the linear track of the irradiation position of the ultraviolet light, and it is easy to produce a relatively low portion of ultraviolet irradiation between the portions. Therefore, it is usually easy to produce striped concave-convex on the cured product of the coating due to the difference in curing shrinkage between the above-mentioned portions. However, in the present embodiment, as described above, the absolute value of the difference between the first curing shrinkage of the composition (X) and the second curing shrinkage is small, so that even if the difference in the irradiation amount of ultraviolet light is locally generated in the coating of the composition (X), it is not easy to produce the difference in shrinkage, so it can be inferred that the cured product is not easy to produce concave-convex.
[0021] It is more preferred if the absolute value of the difference between the first cure shrinkage and the second cure shrinkage is 1.5 percentage points or less, and further preferred if it is 1 percentage point or less. The smaller the value, the more preferred, and ideally 0 percentage points. It should be noted that examples of specific determination methods and determination conditions for the first cure shrinkage and the second cure shrinkage of the composition (X) are described in detail in the Examples column described later.
[0022] A coating film with a thickness of 10 μm was prepared from the composition (X) and irradiated at an intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 When the coating film is irradiated with ultraviolet rays having a peak wavelength of 395 nm under the conditions of the conditions of the invention, the reaction rate of the photopolymerizable compound (A) in the composition (X) is preferably 80% or more. In this case, even if a difference in the amount of ultraviolet rays is locally generated when the composition (X) is irradiated with ultraviolet rays to cure it, a difference in the reaction rate of the photopolymerizable compound (A) is not easily generated in the cured product. Therefore, it is particularly difficult to generate a difference in the amount of shrinkage during the curing of the composition (X), and therefore, the cured product is not easy to produce bumps. This characteristic of the composition (X) can be achieved by improving the reactivity of the photopolymerizable compound (A) by adjusting the composition (X) described later. It should be noted that the reduction rate of the reactive functional groups in the photopolymerizable compound (A) is defined as the reaction rate of the photopolymerizable compound (A), and the reduction rate is obtained based on the results of analyzing the composition (X) by infrared spectroscopy before and after irradiation with ultraviolet rays. An example of a specific method for determining the reaction rate is described in the embodiment column described later.
[0023] Composition (X) can be used to manufacture optical components, and light-emitting devices having optical components can also be manufactured. It should be noted that the use of composition (X) is not limited to the manufacture of optical components, but can also be applied to various uses utilizing the characteristics of composition (X).
[0024] Composition (X) is preferably formed by inkjet method. In this case, it is easy to make the cured product of composition (X) with good positional accuracy. In addition, compared with the situation of forming by printing method accompanied by contact such as screen printing method, when composition (X) is formed by inkjet method, foreign matter is not easy to mix in composition (X) and its cured product, therefore, the yield rate when making optical components is not easy to deteriorate.
[0025] At least one of the viscosity at 25°C and the viscosity at 40°C of the composition (X) is preferably 30 mPa·s or less.
[0026] When the viscosity of the composition (X) at 25°C is 30 mPa·s or less, the composition (X) can be easily molded at room temperature, and in particular, can be easily molded by an inkjet method. The viscosity is more preferably 25 mPa·s or less, further preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. The viscosity is also preferably 1 mPa·s or more, and further preferably 5 mPa·s or more.
[0027] When the viscosity of the composition (X) at 40°C is 30mPa·s or less, no matter what the viscosity of the composition (X) at room temperature is, as long as the composition (X) is slightly heated, it can be made low-viscosity. Therefore, if heated, the composition (X) can be easily formed, especially easily formed by an inkjet method. In addition, since it can be made low-viscosity without significantly heating the composition (X), it is not easy to cause changes in the composition (X) caused by the volatilization of the components in the composition (X). The viscosity is more preferably less than 25mPa·s, more preferably less than 20mPa·s, and particularly preferably less than 15mPa·s. The viscosity is also preferably more than 1mPa·s, and more preferably more than 5mPa·s.
[0028] Such low viscosity of the composition (X) at 25°C or 40°C can be achieved by the composition (X) described in detail below. The method and conditions for measuring the viscosity of the composition (X) at 25°C and 40°C are described in detail in the Examples section below.
[0029] The ratio of the outgassing gas generated when the cured product of the composition (X) is heated at 80°C for 30 minutes is preferably 500 ppm or less. In this case, it is not easy to generate outgassing gas from the cured product. Therefore, for example, it is not easy to generate voids caused by outgassing gas in a light-emitting device having an optical component including a cured product. Therefore, it is not easy for water and oxygen to reach the light-emitting element through the voids, so that the light-emitting element is not easy to deteriorate due to water and oxygen.
[0030] The composition (X) preferably does not contain a solvent or the content of the solvent is 1% by mass or less. In this case, it is not easy to generate outgassing from the solvent from the composition (X) and the cured product of the composition (X). In addition, when manufacturing optical components and light-emitting devices, a drying process for removing the solvent from the composition (X) and the cured product may not be required. It is also possible to have a drying process for removing the solvent from at least one of the composition (X) and the cured product, in which case it is possible to reduce the heating temperature in the drying process and shorten the heating time. Therefore, it is not easy to generate outgassing from the optical component without reducing the manufacturing efficiency of the optical component and the light-emitting device. In addition, especially in the case where the composition (X) is formed by an inkjet method, the reduction in thickness caused by the volatilization of the solvent from the formed composition (X) is not easy to occur, so the reduction in the thickness of the optical component is not easy to occur. Therefore, it is possible to ensure the thickness of the optical component as much as possible while forming by an inkjet method. The content of the solvent is more preferably less than 0.5% by mass, further preferably less than 0.3% by mass, and particularly preferably less than 0.1% by mass. It is particularly preferred that the composition (X) contains no solvent or contains only an inevitably mixed solvent.
[0031] The glass transition temperature of the cured product of the composition (X) is preferably 80°C or more. That is, the composition (X) preferably has the property of becoming a cured product with a glass transition temperature of 80°C or more by curing. In this case, the cured product can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by a temperature rise, the cured product is not easy to deteriorate. Therefore, for example, when a layer of inorganic material overlapping with an optical component (such as a passivation layer 6) is made by a vapor deposition method such as a plasma CVD method, the optical component is not easy to deteriorate even if the optical component is heated. In addition, by improving the heat resistance, the optical component can also be made suitable for vehicle-mounted uses that require strict heat resistance. The glass transition temperature of the cured product is more preferably 90°C or more, and further preferably 100°C or more. The glass transition temperature of the cured product can be achieved by the composition of the composition (X) described in detail below.
[0032] The volatility of 20 mg of the composition (X) when subjected to heat treatment at 100°C for 30 minutes using a thermogravimetric analyzer is preferably 40% or less. The volatility of the composition (X) is defined as the percentage of the weight loss of the composition (X) after treatment (the difference between the weight of the composition (X) before treatment and the weight of the composition (X) after treatment) relative to the weight of the composition (X) before treatment. In this case, since the volatility of the composition (X) is low, the storage stability of the composition (X) can be improved. In addition, it is not easy to generate outgassing from the cured product and optical components of the composition (X). Therefore, it is more difficult to generate voids caused by outgassing in the light-emitting device. The volatility of the composition (X) can be obtained by using a thermogravimetric analyzer to heat treat 20 mg of the composition (X) at 100°C for 30 minutes and calculate the weight loss of the weight after treatment relative to the weight before treatment. When 20 mg of the composition (X) is heated at 100°C for 30 minutes using a thermogravimetric analyzer, the volatility is more preferably 30% or less, and even more preferably 20% or less. The lower limit of the volatility of the composition (X) is not particularly limited, and may be, for example, 0.1% or more.
[0033] The components contained in the composition (X) will be described in more detail.
[0034] The photopolymerizable compound (A) is a component that can undergo polymerization reaction by irradiation with ultraviolet light in the presence or absence of a photopolymerization initiator (B). The photopolymerization initiator (B) may contain a curing catalyst. The photopolymerizable compound (A) contains, for example, at least one component selected from a monomer, an oligomer, and a prepolymer.
[0035] The photopolymerizable compound (A) contains, for example, at least one of a radical polymerizable compound (A1) and a cation polymerizable compound (A2). When the photopolymerizable compound (A) contains a radical polymerizable compound (A1), the photopolymerization initiator (B) preferably contains a photoradical polymerization initiator (B1). When the photopolymerizable compound (A) contains a cation polymerizable compound (A2), the photopolymerization initiator (B) preferably contains a photocationic polymerization initiator (B2) (cationic curing catalyst).
[0036] The case where the photopolymerizable compound (A) contains the radical polymerizable compound (A1) is described.
[0037] The radical polymerizable compound (A1) preferably contains an acrylic compound (Y). The acrylic compound (Y) has one or more (meth)acryloyl groups in one molecule.
[0038] The viscosity of the acrylic compound (Y) as a whole at 25°C is preferably 50 mPa·s or less. In this case, the acrylic compound (Y) can make the composition (X) particularly low in viscosity. The viscosity of the acrylic compound (Y) as a whole is further preferably 30 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (Y) as a whole is, for example, 3 mPa·s or more.
[0039] The viscosity of the acrylic compound (Y) as a whole at 40°C is also preferably 50 mPa·s or less. In this case, the acrylic compound (Y) can make the composition (X) particularly low in viscosity when heated. The viscosity of the acrylic compound (Y) as a whole is further preferably 30 mPa·s or less, and particularly preferably 20 mPa·s or less. In addition, the viscosity of the acrylic compound (Y) as a whole is, for example, 3 mPa·s or more.
[0040] The percentage of the component with a boiling point of 270° C. or higher in the acrylic compound (Y) is preferably 80% by mass or higher. In this case, the storage stability of the composition (X) is particularly unlikely to be impaired, and outgassing from the cured product is particularly unlikely to occur. The percentage of the component with a boiling point of 280° C. or higher in the acrylic compound (Y) is more preferably 80% by mass or higher.
[0041] The acrylic compound (Y) preferably contains a component having a viscosity of 20 mPa·s or less at 25° C. In this case, the viscosity of the composition (X) can be reduced.
[0042] The ratio of the component having a viscosity of 20 mPa·s or less at 25° C. to the total amount of the acrylic compound (Y) is preferably 50% by mass or more and 100% by mass or less. In this case, the viscosity of the composition (X) can be particularly low, and the composition (X) can be applied particularly easily by an inkjet method. The ratio is more preferably 60% by mass or more, and further preferably 70% by mass or more. In addition, the ratio is even more preferably 95% by mass or less, and even more preferably 90% by mass or less.
[0043] The component having a viscosity of 20 mPa·s or less at 25°C preferably contains a compound having a glass transition temperature of 80°C or more. In this case, the viscosity of the composition (X) can be reduced and the glass transition temperature of the cured product can be increased. The component preferably contains a compound having a glass transition temperature of 90°C or more, and more preferably contains a compound having a glass transition temperature of 100°C or more. The upper limit of the glass transition temperature of the compound contained in the component is not limited, for example, it is 150°C or less.
[0044] The compounds that may be contained in the acrylic compound (Y) are described.
[0045] The acrylic compound (Y) preferably contains a multifunctional acrylic compound (Y1), which has two or more free radical polymerizable functional groups including a (meth)acryloyl group in one molecule. In this case, the multifunctional acrylic compound (Y1) can increase the glass transition temperature of the cured product, and therefore, the heat resistance of the cured product can be improved. The proportion of the multifunctional acrylic compound (Y1) is preferably 50% by mass or more and 100% by mass or less relative to the acrylic compound (Y) as a whole. The acrylic compound (Y) may contain only the multifunctional acrylic compound (Y1).
[0046] The polyfunctional acrylic compound (Y1) contains, for example, 1,3-butanediol di(meth)acrylate, 1,4-butanediol oligoacrylate, diethylene glycol diacrylate, 1,6-hexanediol oligoacrylate, neopentyl glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, cyclohexanedimethanol diacrylate, tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, pentaerythritol tetraacrylate, propoxylated (2) neopentyl glycol diacrylate, trimethylolpropane triacrylate, tri(2-hydroxyethyl) Isocyanurate triacrylate, pentaerythritol triacrylate, ethoxylated (3) trimethylolpropane triacrylate, propoxylated (3) glycerol triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, ethoxylated (4) pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, 2-(2-ethoxyethoxy)ethyl acrylate, hexanediol diacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, tripropylene glycol triacrylate, dipentaerythritol hexaacrylate, ethylene glycol diacrylate, 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate Ester, polypropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,9-nonanediol diacrylate, tetraethylene glycol diacrylate, 2-n-butyl-2-ethyl-1,3-propanediol diacrylate, hydroxypivalic acid neopentyl glycol diacrylate, hydroxypivalic acid trimethylolpropane triacrylate, ethoxylated phosphoric acid triacrylate, ethoxylated tripropylene glycol diacrylate, neopentyl glycol modified trimethylolpropane diacrylate, stearic acid modified pentaerythritol diacrylate, tetramethylolpropane triacrylate, tetramethylolmethane triacrylate, caprolactone modified trimethylolpropane triacrylate, propoxylated glycerol tripropylene At least one compound selected from the group consisting of esters, tetramethylolmethane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, caprolactone-modified dipentaerythritol hexaacrylate, dipentaerythritol hydroxypentaacrylate, neopentyl glycol oligoacrylate, trimethylolpropane oligoacrylate, pentaerythritol oligoacrylate, ethoxylated neopentyl glycol di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate and 2-(2-vinyloxyethoxy)ethyl acrylate.
[0047] The acrylic acid equivalent of the polyfunctional acrylic compound (Y1) is preferably 150 g / eq or less, more preferably 90 g / eq or more and 150 g / eq or less. The weight average molecular weight of the polyfunctional acrylic compound (Y1) is, for example, 100 or more and 1000 or less, more preferably 200 or more and 800 or less.
[0048] The polyfunctional acrylic compound (Y1) preferably further contains a compound (Y11) having a structure represented by the following formula (200).
[0049] CH2=CR 1 -COO-(R 3 -O)n-CO-CR 2 =CH2…(200)
[0050] In formula (200), R 1 and R 2 are each hydrogen or methyl, n is an integer greater than 1, R 3 is an alkylene group having 1 or more carbon atoms. When n is 2 or more, a plurality of R 3 They can be the same or different from each other.
[0051] Compound (Y11) has a structure represented by formula (200), especially R 3 The carbon number of the solid is 3 or more, which makes it difficult to improve the affinity of the solidified material with water. 3 The number of carbon atoms is, for example, 1 to 15, preferably 3 to 15. In addition, compound (Y11) has a structure represented by formula (200), especially having two (meth)acryloyl groups in one molecule, thereby increasing the glass transition temperature of the cured product, thereby increasing the heat resistance of the cured product. In addition, n in formula (200) is, for example, an integer of 1 to 12.
[0052] The percentage of compound (Y11) relative to the acrylic compound (Y) is preferably 50% by mass or more. In this case, the affinity of the cured product for water is particularly difficult to improve. The percentage of compound (Y11) relative to the acrylic compound (Y) is, for example, 100% by mass or less, or 95% by mass or less, preferably 80% by mass or less.
[0053] It is particularly preferred that the compound (Y11) contains a component having a boiling point of 270°C or more. That is, the acrylic compound (Y) preferably contains a component having a structure represented by formula (200) and a boiling point of 270°C or more. In this case, the acrylic compound (Y) is not easy to volatilize from the composition (X) during storage of the composition (X) and when the composition (X) is heated. Therefore, the storage stability of the composition (X) is not easily impaired. In addition, even if the compound (Y11) remains in the cured product of the composition (X) without reacting, it is not easy to generate outgassing caused by the compound (Y11) from the cured product. Therefore, it is not easy to generate voids caused by outgassing in the light-emitting device 1. If there are voids in the light-emitting device 1, moisture may penetrate into the light-emitting element 4 through the voids, and if voids are not easy to generate, moisture is not easy to penetrate into the light-emitting element 4. The boiling point is the boiling point at normal pressure converted from the boiling point at reduced pressure, and can be determined, for example, by the method described in Science of Petroleum, Vol. II. P. 1281 (1938). More preferably, compound (Y11) contains a component having a boiling point of 280° C. or higher.
[0054] The percentage of compound (Y11) relative to the acrylic compound (Y) is preferably 50% by mass or more. In this case, the storage stability of the composition (X) can be effectively improved and the generation of outgassing from the cured product can be effectively reduced, and the affinity of the cured product for water is particularly unlikely to increase. The percentage of compound (Y11) relative to the acrylic compound (Y) is, for example, 100% by mass or less, or 95% by mass or less, and preferably 80% by mass or less.
[0055] The viscosity of the compound (Y11) at 25°C is preferably 25 mPa·s or less. In this case, the compound (Y11) can reduce the viscosity of the composition (X). The viscosity of the compound (Y11) at 25°C is more preferably 25 mPa·s or less, further preferably 20 mPa·s or less, and particularly preferably 15 mPa·s or less. In addition, the viscosity of the compound (Y11) at 25°C is, for example, 1 mPa·s or more, preferably 3 mPa·s or more, and further preferably 5 mPa·s or more.
[0056] The compound (Y11) contains, for example, at least one compound selected from the group consisting of alkylene glycol di(meth)acrylates, polyalkylene glycol di(meth)acrylates, and alkylene oxide-modified alkylene glycol di(meth)acrylates.
[0057] Alkylene glycol di(meth)acrylate is a compound wherein n is 1 in formula (200). In this case, R in formula (200) 3 The number of carbon atoms in R is preferably 4 to 12. 3The alkylene glycol di(meth)acrylate may be straight-chain or branched. In particular, the alkylene glycol di(meth)acrylate preferably contains at least one compound selected from 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, and 1,12-dodecanediol dimethacrylate. The alkylene glycol di(meth)acrylate preferably contains a product selected from the group consisting of SR213 manufactured by Sartomer, V195 manufactured by Osaka Organic Chemical Industry Co., Ltd., SR212 manufactured by Sartomer, SR247 manufactured by Sartomer, LIGHT ACRYLATE manufactured by Kyoei Chemical Industry Co., Ltd. NP-A, product number SR238NS manufactured by Sartomer, product number V230 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number HDDA manufactured by Daicel, product number 1,6HX-A manufactured by Kyoei Chemical Industry Co., Ltd., product number V260 manufactured by Osaka Organic Chemical Industry Co., Ltd., product number 1,9-ND-A manufactured by Kyoei Chemical Industry Co., Ltd., product number A-NOD-A manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number CD595 manufactured by Sartomer, product number SR214NS manufactured by Sartomer, product number BD manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product number SR297 manufactured by Sartomer, product number SR248 manufactured by Sartomer, product name LIGHT ESTER NP manufactured by Kyoei Chemical Industry Co., Ltd., product number SR239NS manufactured by Sartomer, product name LIGHT ESTER manufactured by Kyoei Chemical Industry Co., Ltd. 1,6HX, product number HD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,9ND manufactured by Kyoei Chemical Industry Co., Ltd., product number NOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ESTER 1,10DC manufactured by Kyoei Chemical Industry Co., Ltd., product number DOD-N manufactured by Shin-Nakamura Chemical Industry Co., Ltd. and at least one compound selected from the group consisting of product number SR262 manufactured by Sartomer.
[0058] The polyalkylene glycol di(meth)acrylate is, for example, a compound wherein n in the formula (200) is 2 or more. n is, for example, 2 to 10, preferably 2 to 7, more preferably 2 to 6, and even more preferably 2 to 3. 3The number of carbon atoms is, for example, 2 to 7, preferably 2 to 5. The more carbon atoms there are, the higher the hydrophobicity of the cured product is, and the less likely it is for water to penetrate the cured product. The polyalkylene glycol di(meth)acrylate particularly preferably contains at least one compound selected from diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, hexaethylene glycol dimethacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, tributylene glycol diacrylate (tritetramethylene glycol diacrylate), polyethylene glycol 200 dimethacrylate, and polyethylene glycol 200 diacrylate. The polyalkylene glycol di(meth)acrylate is particularly preferably selected from the group consisting of product number SR230 manufactured by Sartomer, product number SR508NS manufactured by Sartomer, product number DPGDA manufactured by Daicel, product number SR306NS manufactured by Sartomer, product number TPGDA manufactured by Daicel, product number V310HP manufactured by Osaka Organic Chemical Industry Co., Ltd., product number APG200 manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name LIGHT ACRYLATE PTMGA-250 manufactured by Kyoei Chemical Industry Co., Ltd., product number SR231NS manufactured by Sartomer, product name LIGHT ESTER 2EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR205NS manufactured by Sartomer, product name LIGHT ESTER 3EG manufactured by Kyoei Chemical Industry Co., Ltd., product number SR210NS manufactured by Sartomer, product name LIGHT ESTER At least one compound selected from the group consisting of 4EG, ACRYESTER HX manufactured by Mitsubishi Chemical Corporation, and 3PG manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0059] The alkylene oxide-modified alkylene glycol di(meth)acrylate includes, for example, propylene oxide-modified neopentyl glycol. In addition, the alkylene oxide-modified alkylene glycol di(meth)acrylate includes, for example, EBECRYL145 manufactured by Daicel.
[0060] When the acrylic compound (Y) contains a compound (Y11) having a structure represented by the formula (200), the compound (Y11) preferably does not contain a compound in which the value of n in the formula (200) is 5 or more. 3-O)n is a polyethylene glycol skeleton, it is particularly preferred that the compound whose n value in the formula (200) is greater than 5 is not included. Even if the compound (Y11) contains a compound whose n value in the formula (200) is greater than 5, it is preferred that the percentage of the compound whose n value in the formula (200) is greater than 5 relative to the acrylic compound (Y) is 20% by mass or less. In addition, even if the compound (Y11) contains a compound whose n value in the formula (200) is greater than 5, it is preferred that the compound (Y11) does not contain a compound whose n value is greater than 9, and further preferably does not contain a compound whose n value is greater than 7. In these cases, the viscosity of the composition (X) is particularly unlikely to increase.
[0061] It is particularly preferred if the multifunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate. Polyalkylene glycol di(meth)acrylate has a low viscosity and is not easily volatile, so it can help to reduce the viscosity of the composition (X), and can help to improve the storage stability of the composition (X) and reduce the outgassing from the cured product.
[0062] In the case where the multifunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate, the ratio of polyalkylene glycol di(meth)acrylate to the acrylic compound (Y) is preferably 40% by mass or more and 80% by mass or less. If the ratio of polyalkylene glycol di(meth)acrylate is 40% by mass or more, the viscosity of the composition (X) can be effectively reduced. If the ratio of polyalkylene glycol di(meth)acrylate is 80% by mass or less, the ratio of compounds having three or more (meth)acryloyl groups in the molecule increases, and the reactivity of the composition (X) and the glass transition temperature of the cured product can be improved. The ratio is more preferably 42% by mass or more and 75% by mass or less, and more preferably 45% by mass or more and 70% by mass or less.
[0063] The multifunctional acrylic compound (Y1) may contain a compound having three or more free radical polymerizable functional groups including a (meth)acryloyl group in one molecule. In this case, the multifunctional acrylic compound (Y1) may contain, for example, at least one selected from trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and pentaerythritol tetra(meth)acrylate. In this case, the glass transition temperature of the cured product can be particularly increased, and therefore, the heat resistance of the cured product can be particularly increased.
[0064] The multifunctional acrylic compound (Y1) particularly preferably contains pentaerythritol tetra(meth)acrylate. In this case, the glass transition temperature of the cured product can be particularly increased, and the reactivity of the composition (X) can be increased. If the reactivity of the composition (X) is increased, the composition (X) can be easily cured even in an oxygen-containing environment such as an atmospheric atmosphere.
[0065] When the multifunctional acrylic compound (Y1) contains pentaerythritol tetra(meth)acrylate, the ratio of pentaerythritol tetra(meth)acrylate to the acrylic compound (Y) is preferably 0.5% by mass or more and 10% by mass or less. In this case, both high reactivity and low viscosity of the composition (X) can be achieved. The ratio is more preferably 1% by mass or more and 9% by mass or less, and further preferably 2% by mass or more and 8% by mass or less.
[0066] The multifunctional acrylic compound (Y1) may have at least one of a benzene ring, an alicyclic ring and a polar group. The polar group is, for example, at least one of an OH group and an NHCO group. In this case, the shrinkage of the composition (X) during curing can be particularly reduced. In addition, the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide can also be improved. The multifunctional acrylic compound (Y1) particularly preferably contains at least one compound selected from tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, bisphenol F polyethoxy diacrylate, trimethylolpropane triacrylate and pentaerythritol triacrylate. These compounds can particularly reduce the shrinkage of the composition (X) during curing. In addition, these compounds can also improve the adhesion between the cured product and inorganic compounds such as silicon nitride and silicon oxide.
[0067] If the adhesion between the cured product and the inorganic material is improved, when an optical component and a film made of an inorganic material (inorganic film) such as a SiN film are superimposed, high adhesion between the optical component and the inorganic film can be easily obtained.
[0068] It is particularly preferred that the multifunctional acrylic compound (Y1) contains polyalkylene glycol di(meth)acrylate and pentaerythritol tetra(meth)acrylate. In this case, the composition (X) has low viscosity and excellent reactivity. Therefore, even in an oxygen-containing environment such as an atmospheric atmosphere, the composition (X) can be easily cured.
[0069] The acrylic compound (Y) also preferably contains a monofunctional acrylic compound (Y2) having only one (meth)acryloyl group as a radical polymerizable functional group in one molecule. The monofunctional acrylic compound (Y2) can suppress shrinkage of the composition (X) during curing.
[0070] In the case where the acrylic compound (Y) contains a monofunctional acrylic compound (Y2), the amount of the monofunctional acrylic compound (Y2) is preferably greater than 0% by mass and less than 50% by mass relative to the total amount of the acrylic compound (Y). If the amount of the monofunctional acrylic compound (Y2) is greater than 0% by mass, the shrinkage during the curing of the composition (X) can be suppressed. In addition, if the amount of the monofunctional acrylic compound (Y2) is less than 50% by mass, the amount of the multifunctional acrylic compound (Y1) can be more than 50% by mass, thereby being able to particularly improve the heat resistance of the cured product. The amount of the monofunctional acrylic compound (Y2) is further preferably more than 5% by mass, and is also further preferably less than 30% by mass, and is particularly preferred if it is less than 20% by mass.
[0071] The monofunctional acrylic compound (Y2) contains, for example, tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, 2-methoxyethyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, 3-methoxybutyl acrylate, ethoxyethyl acrylate, butoxyethyl acrylate, ethoxydiethylene glycol acrylate, methoxyethyl acrylate, diethylene glycol monoethyl acrylate, Ether acrylate, cyclic trimethylolpropane formal monoacrylate, imide acrylate, isopentyl acrylate, ethoxylated succinic acid acrylate, trifluoroethyl acrylate, ω-carboxy polycaprolactone monoacrylate, cyclohexyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, stearyl acrylate, diethylene glycol monobutyl ether acrylate, lauryl acrylate, isodecyl acrylate, 3,3,5-trimethylcyclohexanol acrylate, isooctyl acrylate, octyl / decyl acrylate, propylene Tridecyl acrylate, caprolactone acrylate, ethoxylated (4) nonylphenol acrylate, methoxy polyethylene glycol (350) monoacrylate, methoxy polyethylene glycol (550) monoacrylate, phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, caprolactone modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated propylene The invention relates to a novel polyol having a molecular weight of 400 μm and a molecular weight of 400 μm. The invention relates to a polyol having a molecular weight of 400 μm and a molecular weight of 400 μm. The invention relates to a polyol having a molecular weight of 400 μm and a molecular weight of 400 μm. The invention relates to a polyol having a molecular weight of 400 μm and a molecular weight of 400 μm.
[0072] The monofunctional acrylic compound (Y2) may contain at least one compound selected from the group consisting of a compound having an alicyclic structure and a compound having a cyclic ether structure.
[0073] The compound having an alicyclic structure contains, for example, at least one compound selected from phenoxyethyl acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl acrylate, methylphenoxyethyl acrylate, 4-tert-butylcyclohexyl acrylate, caprolactone-modified tetrahydrofurfuryl acrylate, tribromophenyl acrylate, ethoxylated tribromophenyl acrylate, 2-phenoxyethyl acrylate, ethylene oxide adduct of 2-phenoxyethyl acrylate, propylene oxide adduct of 2-phenoxyethyl acrylate, acryloyl morpholine, morpholin-4-yl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate and 1,4-cyclohexanedimethanol monoacrylate.
[0074] The number of ring members of the cyclic ether structure in the compound having a cyclic ether structure is preferably 3 or more, more preferably 3 or more and 4 or less. The number of carbon atoms contained in the cyclic ether structure is preferably 2 or more and 9 or less, more preferably 2 or more and 6 or less. The compound having a cyclic ether structure contains, for example, at least one compound selected from 3-methacryloyloxymethylcyclohexene oxide and 3-acryloyloxymethylcyclohexene oxide.
[0075] The acrylic compound (Y) may contain a compound having silicon in its molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. The compound having silicon in its molecular skeleton may contain at least one compound selected from 3-(trimethoxysilyl)propyl acrylate (e.g., product number KBM5103 manufactured by Shin-Etsu Chemical Co., Ltd.) and an alkoxysilane oligomer containing a (meth) acrylic group (e.g., product number KR-513 manufactured by Shin-Etsu Chemical Co., Ltd.).
[0076] The acrylic compound (Y) may contain a compound having phosphorus in its molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. The compound having phosphorus in its molecular skeleton includes, for example, acid phosphoxy (meth) acrylates such as acid phosphoxypolyoxypropylene glycolmonomethacrylate.
[0077] The acrylic compound (Y) may contain a compound having nitrogen in its molecular skeleton. In this case, the adhesion between the cured product and the inorganic material is improved. In addition, the reactivity of the acrylic compound (Y) is easily improved, so it is not easy to generate outgassing from the cured product. The compound having nitrogen in its molecular skeleton includes, for example, a compound having a morpholine skeleton such as acryloylmorpholine, morpholine-4-yl acrylate, diethylacrylamide, dimethylaminopropylacrylamide and at least one compound selected from pentamethylpiperidinyl methacrylate.
[0078] Acrylic acid compound (Y) particularly preferably contains a compound with a morpholine skeleton. In this case, the reactivity of the composition (X) can be further improved, even in an atmospheric atmosphere, the curability of the composition (X) can be further improved. Acrylic acid compound (Y) particularly preferably contains at least one of acryloyl morpholine and morpholine acrylate-4-base ester. In this case, the shrinkage during the curing of the composition (X) can be suppressed. In addition, the viscosity of acryloyl morpholine and morpholine acrylate-4-base ester is low, so these compounds are not easy to increase the viscosity of the composition (X). In addition, these compounds are not easy to volatilize, so it is easy to improve the storage stability of the composition (X).
[0079] The ratio of the compound with morpholine skeleton to the acrylic compound (Y) is preferably 5% by mass or more and 50% by mass or less. In this case, there is an advantage that it is not easy to generate outgassing from the cured product of the composition (X). The ratio is more preferably 7% by mass or more and 45% by mass or less, and further preferably 10% by mass or more and 40% by mass or less.
[0080] The acrylic compound (Y) may contain a compound having an isobornyl skeleton. The compound having an isobornyl skeleton may contain, for example, one or more compounds selected from the group consisting of isobornyl acrylate and isobornyl methacrylate.
[0081] The acrylic compound (Y) may contain the following components, which include a compound having at least one skeleton selected from a dicyclopentadiene skeleton, a dicyclopentyl skeleton, a dicyclopentenyl skeleton, and a bisphenol skeleton. Specifically, the acrylic compound (Y) may contain, for example, at least one compound selected from tricyclodecane dimethanol diacrylate, bisphenol A polyethoxy diacrylate, and bisphenol F polyethoxy diacrylate. In this case, the adhesion of the cured product to the inorganic material can be improved.
[0082] The acrylic compound (Y) may contain a compound represented by the following formula (100). In this case, the reactivity of the composition (X) can be improved, and the adhesion between the cured product and the inorganic material can be improved.
[0083]
Chemical formula 1
[0084]
[0085] In formula (100), R 0 is H or methyl. X is a single bond or a divalent hydrocarbon group. 1 ~R 11 Each is H, alkyl or -R 12 -OH, R 12 is an alkylene group and R 1~R 11 At least one of them is alkyl or -R 12 -OH.R 1 ~R 11 There is no chemical bonding between them.
[0086] Specifically, for example, the acrylic compound (Y) may contain at least one compound selected from the group consisting of a compound represented by the following formula (110), a compound represented by the following formula (120), and a compound represented by the following formula (130).
[0087]
Chemical formula 2
[0088]
[0089] The radical polymerizable compound (A1) may contain a radical polymerizable compound (Z) other than the acrylic compound (Y). The amount of the radical polymerizable compound (Z) relative to the total amount of the acrylic compound (Y) and the radical polymerizable compound (Z) is, for example, 10% by mass or less. The radical polymerizable compound (Z) may contain any one or both of a polyfunctional radical polymerizable compound (Z1) having two or more radical polymerizable functional groups in one molecule and a monofunctional radical polymerizable compound (Z2) having only one radical polymerizable functional group in one molecule. The polyfunctional radical polymerizable compound (Z1) may, for example, contain at least one compound selected from aromatic carbamate oligomers, aliphatic carbamate oligomers, epoxy acrylate oligomers, polyester acrylate oligomers and other special oligomers having two or more ethylenic double bonds in one molecule. It should be noted that the components that the polyfunctional radical polymerizable compound (Z1) may contain are not limited to the above components. The monofunctional free radical polymerizable compound (Z2) contains, for example, at least one compound selected from N-vinylformamide, vinyl caprolactam, vinyl pyrrolidone, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, 1,2-butylene oxide, 1,3-butadiene monooxide, 1,2-epoxydodecane, epichlorohydrin, 1,2-epoxydecane, styrene oxide, hexyl oxide, 3-vinyl hexyl oxide, 4-vinyl hexyl oxide, N-vinyl pyrrolidone and N-vinyl caprolactam. It should be noted that the components that the monofunctional free radical polymerizable compound (Z2) can contain are not limited to the above components.
[0090] When the radical polymerizable compound (A1) contains a radical polymerizable compound (Z), the radical polymerizable compound (Z) may contain a compound having nitrogen in its molecular skeleton. The compound having nitrogen in its molecular skeleton, for example, includes at least one compound selected from N-vinylformamide, N-vinylpyrrolidone and N-vinylcaprolactam. In this case, similarly to the case where the acrylic compound (Y) contains a compound having nitrogen in its molecular skeleton, the adhesion between the cured product and the inorganic material is improved.
[0091] In other words, it is preferred that the radical polymerizable compound (A1) contains a compound having nitrogen in the molecular skeleton. The compound having nitrogen in the molecular skeleton may contain a compound contained in an acrylic compound (Y), or may contain a compound contained in a radical polymerizable compound (Z). In this case, the adhesion between the cured product and the inorganic material is improved. The ratio of the compound having nitrogen in the molecular skeleton to the entire radical polymerizable compound (A1) is preferably 5% by mass or more and 80% by mass or less. By making the ratio 5% by mass or more, the adhesion between the cured product and the inorganic material is particularly easy to improve. If the ratio is 80% by mass or less, the compound having nitrogen in the molecular skeleton is not easy to hinder the storage stability of the composition (X), and splashing (Japanese: サテライト) is not easy to occur when the composition (X) is sprayed by an inkjet method. Therefore, it is not easy to hinder the inkjet property of the composition (X). In addition, it is not easy to produce outgassing caused by the compound having nitrogen in the molecular skeleton. The ratio is more preferably 10% by mass or more and 70% by mass or less, further preferably 20% by mass or more and 60% by mass or less, and particularly preferably 25% by mass or more and 50% by mass or less.
[0092] The total amount of monofunctional compounds in the radical polymerizable compound (A1) (i.e., the total amount of the monofunctional acrylic compound (Y2) and the monofunctional radical polymerizable compound (Z2)) is preferably 70% by mass or less relative to the radical polymerizable compound (A1). In this case, it is not easy to cause the generation of outgassing caused by the monofunctional compound. The ratio is more preferably 60% by mass or less, and further preferably 50% by mass or less.
[0093] The radical polymerizable compound (A1) particularly preferably contains at least one selected from acryloyl morpholine, morpholine-4-yl acrylate, diethyl acrylamide and dimethyl acrylamide. In this case, it is easy to reduce the absolute value of the difference between the first cure shrinkage and the second cure shrinkage. The total percentage of acryloyl morpholine, morpholine-4-yl acrylate, diethyl acrylamide and dimethyl acrylamide relative to the radical polymerizable compound (A]) is preferably 15% by mass or more. In this case, it is particularly easy to achieve the above-mentioned cure shrinkage difference. The percentage is more preferably 25% by mass or more, and more preferably 35% by mass or more. The upper limit of the percentage is not particularly limited, for example, 100% by mass or less. The percentage is preferably 85% by mass or less, in which case, it is easy to adjust the hardness of the cured film and improve flexibility. The percentage is more preferably 70% by mass or less. In addition, in order to reduce the absolute value of the difference between the first cure shrinkage and the second cure shrinkage, the radical polymerizable compound (A1) preferably does not contain isobornyl methacrylate, lauryl methacrylate and 1,6-hexanediol methacrylate.
[0094] The photoradical polymerization initiator (B1) is not particularly limited as long as it is a compound that generates free radical species when irradiated with ultraviolet rays. The photoradical polymerization initiator (B1) contains, for example, at least one compound selected from aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, sulfur compounds (thioxanthone compounds, compounds containing thiophenyl groups, etc.), hexaarylbiimidazole compounds, oxime ester compounds, boric acid ester compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having carbon-halogen bonds, and alkylamine compounds.
[0095] The photoradical polymerization initiator (B1) also preferably contains a component having a sensitizer skeleton in the molecule. The sensitizer skeleton, for example, contains at least one of a 9H-thioxanthen-9-one skeleton and an anthracene skeleton. That is, the photoradical polymerization initiator (B) preferably contains a component having at least one of a 9H-thioxanthen-9-one skeleton and an anthracene skeleton.
[0096] The photo-radical polymerization initiator (B1) also preferably contains an oxime ester photoinitiator. The oxime ester photoinitiator can improve the curability of the composition (X). Therefore, even in an oxygen-containing environment such as an atmospheric atmosphere, the composition (X) can be easily cured, and it is not easy to generate outgassing from the cured product.
[0097] In order to reduce the risk of contamination of the composition (X) and the manufacturing apparatus due to decomposition products generated from the composition (X), and to further reduce the risk of outgassing from the cured product, the oxime ester-based photoinitiator preferably comprises a compound having an aromatic ring, more preferably comprises a compound having a condensed ring containing an aromatic ring, and further preferably comprises a compound having a condensed ring containing a benzene ring and a heterocyclic ring.
[0098] The oxime ester photoinitiator may contain, for example, at least one compound selected from 1,2-octanedione-1-[4-(phenylthio)-2-(o-benzoyl oxime)] and ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(o-acetyl oxime) and oxime ester photoinitiators described in Japanese Patent Application Publication No. 2000-80068, Japanese Patent Application Publication No. 2001-233842, Japanese Table No. 2010-527339, Japanese Table No. 2010-527338, Japanese Patent Application Publication No. 2013-041153 and Japanese Patent Application Publication No. 2015-93842. The oxime ester photoinitiator may contain at least one compound selected from the commercially available Irgacure OXE-02 (manufactured by BASF), ADEKA ARKLS NCI-831, N-1919 (manufactured by ADEKA), and TR-PBG-304 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) having a carbazole skeleton, Irgacure OXE-01, ADEKA ARKLS NCI-930 (manufactured by ADEKA), TR-PBG-345, and TR-PBG-3057 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) having a diphenyl sulfide skeleton, and TR-PBG-365 (manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.) and SPI-04 (manufactured by Samyang) having a fluorene skeleton. In particular, if the oxime ester photoinitiator contains a compound having a diphenyl sulfide skeleton or a fluorene skeleton, the cured product is less likely to be colored by photobleaching, which is preferred from this point of view. From the viewpoint of easily improving exposure sensitivity, it is preferred that the oxime ester-based photoinitiator contains a compound having a carbazole skeleton.
[0099] It is also preferred that the oxime ester photoinitiator contains two or more compounds. In this case, for example, by containing two or more compounds having different exposure sensitivities, the oxime ester photoinitiator can maintain good exposure sensitivity and reduce the amount of the photoradical polymerization initiator (B), thereby making it more difficult to generate outgassing from the cured product.
[0100] The ratio of the photo-radical polymerization initiator (B1) to the radical polymerizable compound (A1) is preferably 6% by mass or more. In this case, the composition (X) can have good ultraviolet curability and can also have good ultraviolet curability under an atmospheric atmosphere. The ratio is more preferably 7% by mass or more, and more preferably 8% by mass or more. In addition, the ratio is, for example, 30% by mass or less, preferably 20% by mass or less, and more preferably 18% by mass or less.
[0101] The radical polymerization initiator (B) preferably contains a radical polymerization initiator (B3) with photobleaching properties. For example, the photo radical polymerization initiator (B1) preferably contains a radical polymerization initiator (B31) with photobleaching properties as the photopolymerization initiator (B3). When the composition (X) is irradiated with ultraviolet rays, the photopolymerization initiator (B3) with photobleaching properties can improve the transparency of the composition (X) and its cured product. Therefore, if the composition (X) is irradiated with ultraviolet rays, the ultraviolet rays easily reach the inside of the composition (X). Therefore, the composition (X) is easily and efficiently cured, and the difference between the first curing shrinkage and the second curing shrinkage is easily reduced.
[0102] The percentage of photopolymerization initiator (B3) relative to photopolymerization initiator (B) is preferably 50% by mass or more. In this case, the difference between the first cure shrinkage and the second cure shrinkage is particularly easy to become smaller. The percentage is more preferably 60% by mass or more, and more preferably 75% by mass or more. The upper limit of the percentage is not particularly limited and can be 100% by mass. That is, the percentage is, for example, 100% by mass or less.
[0103] When the photoradical polymerization initiator (B1) contains the photoradical polymerization initiator (B31), the photoradical polymerization initiator (B31) contains, for example, at least one of a compound having photobleaching properties among oxime ester-based photoinitiators and an acylphosphine oxide-based photoinitiator.
[0104] The oxime ester compound having photobleaching properties contains, for example, at least one of a compound represented by the following formula (401) and a compound represented by the following formula (402). Among them, the compound represented by the formula (402) has particularly high sensitivity, and therefore it is particularly easy to improve the photocurability of the composition (X), and thus it is easy to achieve ultraviolet curability of the composition (X) in an atmospheric atmosphere.
[0105]
Chemical formula 3
[0106]
[0107]
Chemical formula 4
[0108]
[0109] The acylphosphine oxide compound contains, for example, at least one selected from 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0110] The free radical polymerization initiator (B) preferably contains a photopolymerization initiator (B4) having an extinction coefficient of light of 405 nm in wavelength of 5 ml / g·cm or more. For example, the photoradical polymerization initiator (B1) preferably contains a photoradical polymerization initiator (B41) having an extinction coefficient of light of 405 nm in wavelength of 5 ml / g·cm or more as the photopolymerization initiator (B4). When the composition (X) is irradiated with ultraviolet rays, the photopolymerization initiator (B4) can improve the reactivity of the composition (X). Therefore, the difference between the first curing shrinkage and the second curing shrinkage is easy to become smaller.
[0111] The percentage of photopolymerization initiator (B4) relative to photopolymerization initiator (B) is preferably 50% by mass or more. In this case, the difference between the first cure shrinkage and the second cure shrinkage is particularly easy to become smaller. The percentage is more preferably 60% by mass or more, and more preferably 75% by mass or more. The upper limit of the percentage is not particularly limited and can be 100% by mass. That is, the percentage is, for example, 100% by mass or less.
[0112] When the photoradical polymerization initiator (B1) contains a photoradical polymerization initiator (B41), the photoradical polymerization initiator (B41) contains, for example, at least one selected from 2-benzyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone (for example, Irgacure 369 manufactured by BASF), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (for example, Irgacure 819 manufactured by BASF), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (for example, Irgacure TPO manufactured by BASF) and bis(2,4-cyclopentadienyl)bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]titanium (IV) (for example, Irgacure 784 manufactured by BASF).
[0113] It should be noted that the compound contained in the photopolymerization initiator (B3) and the compound contained in the photoradical polymerization initiator (B4) may overlap. That is, when the composition (X) contains the photopolymerization initiator (B3), the photopolymerization initiator (B3) may contain at least a portion of the photoradical polymerization initiator (B4). In addition, when the composition (X) contains the photopolymerization initiator (B4), the photopolymerization initiator (B4) may contain at least a portion of the photoradical polymerization initiator (B3).
[0114] In addition to the photo-radical polymerization initiator (B1), the composition (X) may further contain a polymerization accelerator. The polymerization accelerator may contain, for example, amine compounds such as ethyl p-dimethylaminobenzoate, 2-ethylhexyl p-dimethylaminobenzoate, methyl p-dimethylaminobenzoate, 2-dimethylaminoethyl benzoate, and butoxyethyl p-dimethylaminobenzoate. It should be noted that the components that the polymerization accelerator may contain are not limited to the above components.
[0115] When the photopolymerizable compound (A) contains a cationically polymerizable compound (A2), the cationically polymerizable compound (A2) contains, for example, at least one of a polyfunctional cationically polymerizable compound (W1) and a monofunctional cationically polymerizable compound (W2).
[0116] The polyfunctional cationically polymerizable compound (W1) may contain either or both of a polyfunctional cationically polymerizable compound (W11) not having a siloxane skeleton and a polyfunctional cationically polymerizable compound (W12) having a siloxane skeleton.
[0117] The polyfunctional cationically polymerizable compound (W11) does not have a siloxane skeleton and has two or more cationically polymerizable functional groups in one molecule. The number of cationically polymerizable functional groups in one molecule of the polyfunctional cationically polymerizable compound (W11) is preferably 2 to 4, more preferably 2 to 3.
[0118] The cationically polymerizable functional group is, for example, at least one group selected from an epoxy group, an oxetanyl group, and a vinyl ether group.
[0119] The polyfunctional cationically polymerizable compound (W11) contains, for example, at least one compound selected from the group consisting of polyfunctional alicyclic epoxy compounds, polyfunctional heterocyclic epoxy compounds, polyfunctional oxetane compounds, alkylene glycol diglycidyl ethers, and alkylene glycol monovinyl monoglycidyl ethers.
[0120] The polyfunctional alicyclic epoxy compound contains, for example, either or both of a compound represented by the following formula (1) and a compound represented by the following formula (20).
[0121]
Chemical formula 5
[0122]
[0123] In formula (1), R 1 ~R 18Each is independently a hydrogen atom, a halogen atom or a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably in the range of 1 to 20. Examples of the hydrocarbon group are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl, and propyl groups; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl groups; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene groups. The hydrocarbon group may contain an oxygen atom or a halogen atom. R 1 ~R 18 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.
[0124] In formula (1), X is a single bond or a divalent organic group, and an example of the organic group is -CO-O-CH2-.
[0125] Examples of the compound represented by the formula (1) include a compound represented by the following formula (1a) and a compound represented by the following formula (1b).
[0126]
Chemical formula 6
[0127]
[0128]
Chemical formula 7
[0129]
[0130]
Chemical formula 8
[0131]
[0132] In formula (20), R 1 ~R 12 Each is independently a hydrogen atom, a halogen atom or a hydrocarbon group having 1 to 20 carbon atoms. Examples of the halogen atom are fluorine, chlorine, bromine or iodine. Examples of the hydrocarbon group having 1 to 20 carbon atoms are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl and propyl; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene. The hydrocarbon group having 1 to 20 carbon atoms may contain an oxygen atom or a halogen atom.
[0133] R 1 ~R 12 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.
[0134] Examples of the compound represented by the formula (20) include tetrahydroindene diepoxide represented by the following formula (20a).
[0135]
Chemical formula 9
[0136]
[0137] The polyfunctional heterocyclic epoxy compound includes, for example, a trifunctional epoxy compound represented by the following formula (2).
[0138]
Chemical formula 10
[0139]
[0140] The polyfunctional oxetane compound includes, for example, a bifunctional oxetane compound represented by the following formula (3).
[0141]
Chemical formula 11
[0142]
[0143] The alkylene glycol diglycidyl ether contains, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (4) to (7).
[0144]
Chemical formula 12
[0145]
[0146]
Chemical formula 13
[0147]
[0148]
Chemical formula 14
[0149]
[0150]
Chemical formula 15
[0151]
[0152] The alkylene glycol monovinyl monoglycidyl ether includes, for example, a compound represented by the following formula (8).
[0153]
Chemical formula 16
[0154]
[0155] More specifically, the multifunctional cationic polymerizable compound (W11) may contain, for example, at least one component selected from CELLOXIDE 2021P and CELLOXIDE 8010 manufactured by Daicel, TEPIC-VL manufactured by Nissan Chemical, OXT-221 manufactured by Toagosei, and 1,3-PD-DEP, 1,4-BG-DEP, 1,6-HD-DEP, NPG-DEP and butanediol monovinyl monoglycidyl ether manufactured by Yokkaichi Kogyo.
[0156] The polyfunctional cationically polymerizable compound (W11) preferably further contains a polyfunctional alicyclic epoxy compound. In this case, the composition (X) can have particularly high cationic polymerization reactivity.
[0157] The polyfunctional alicyclic epoxy compound particularly preferably contains one or both of the compound represented by formula (1) and the compound represented by formula (20). In this case, the composition (X) can have higher cationic polymerization reactivity.
[0158] When the polyfunctional alicyclic epoxy compound contains a compound represented by formula (1), the compound represented by formula (1) preferably contains a compound represented by formula (1a). In this case, the composition (X) can have higher cationic polymerization reactivity and particularly low viscosity.
[0159] In addition, in particular, the compound shown in formula (20) has low viscosity, so when containing the compound shown in formula (20), the composition (X) can have good ultraviolet curability while also having particularly low viscosity. In addition, even if the compound shown in formula (20) has low viscosity, it also has the property of being non-volatile. Therefore, even if the composition (X) contains the compound shown in formula (20), the composition (X) is not easy to change its composition due to the volatilization of the compound shown in formula (20). Therefore, the composition (X) can be low-viscosity without compromising storage stability by containing the compound shown in formula (20).
[0160] The compound represented by the formula (20) can be synthesized, for example, by oxidizing a cyclic olefin compound having a tetrahydroindene skeleton using an oxidizing agent.
[0161] The compound represented by formula (20) may include 4 stereoisomers based on the stereo configuration of 2 epoxy rings. The compound represented by formula (20) may include any one of the 4 stereoisomers. That is, the compound represented by formula (20) may contain at least one component selected from the 4 stereoisomers. The ratio of the total amount of the exo-endo form and the endo-endo form in the 4 stereoisomers in the compound represented by formula (20) is preferably 10% by mass or less, and more preferably 5% by mass or less relative to the epoxy compound (A1) as a whole. In this case, the heat resistance of the cured product can be improved. It should be noted that the ratio of a specific stereoisomer in the compound represented by formula (20) can be obtained based on the peak area ratio appearing in the chromatogram obtained by gas chromatography.
[0162] In order to reduce the amount of exo-endo and endo-endo in the compound represented by formula (20), an appropriate method such as a method of precision distilling the compound represented by formula (20) or a method of using column chromatography using silica gel as a filler can be used.
[0163] When the composition (X) contains a polyfunctional cationic polymerizable compound (W11), the ratio of the polyfunctional cationic polymerizable compound (W11) to the total amount of the resin component is preferably 5% by mass or more and 95% by mass or less. It should be noted that the resin component refers to a cationic polymerizable compound in the composition (X), including a polyfunctional cationic polymerizable compound (W1) and a monofunctional cationic polymerizable compound (W2). If the ratio of the polyfunctional cationic polymerizable compound (W11) is 5% by mass or more, the composition (X) can have particularly excellent reactivity during photocationic polymerization, and thereby the cured product can have high strength (hardness). In addition, if the ratio of the polyfunctional cationic polymerizable compound (W11) is 95% by mass or less, when the composition (X) contains a hygroscopic agent (E), the hygroscopic agent (E) can be easily dispersed particularly uniformly in the composition (X). The proportion of the multifunctional cationic polymerizable compound (W11) is more preferably 12% by mass or more, more preferably 15% by mass or more, more preferably 20% by mass or more, and particularly preferably 25% by mass or more. In addition, the proportion of the multifunctional cationic polymerizable compound (W11) is more preferably 85% by mass or less, more preferably 60% by mass or less. For example, the proportion of the multifunctional cationic polymerizable compound (W11) is preferably 20% by mass or more and 60% by mass or less.
[0164] When the polyfunctional cationically polymerizable compound (W11) contains a polyfunctional alicyclic epoxy compound, the polyfunctional alicyclic epoxy compound may be a part of the polyfunctional cationically polymerizable compound (W11) or the whole of the polyfunctional cationically polymerizable compound (W11). The ratio of the polyfunctional alicyclic epoxy compound to the polyfunctional cationically polymerizable compound (W11) is preferably in the range of 15 to 100% by mass. If the ratio is 15% by mass or more, the polyfunctional alicyclic epoxy compound can particularly contribute to the improvement of the ultraviolet curability of the composition (X).
[0165] The multifunctional cationic polymerizable compound (W12) has a siloxane skeleton and two or more cationic polymerizable functional groups in each molecule. The number of cationic polymerizable functional groups in each molecule of the multifunctional cationic polymerizable compound (W12) is preferably 2 to 6, and more preferably 2 to 4. The multifunctional cationic polymerizable compound (W12) can help improve the cationic polymerization reactivity of the composition (X), and can help improve the heat discoloration resistance of the cured product and optical components. The multifunctional cationic polymerizable compound (W12) can also contribute to the low elastic modulus of the cured product and optical components. When the composition (X) contains a hygroscopic agent, the multifunctional cationic polymerizable compound (W12) can also help improve the dispersibility of the hygroscopic agent in the composition (X) and the cured product.
[0166] The polyfunctional cationically polymerizable compound (W12) is preferably liquid at 25° C. In particular, the viscosity of the polyfunctional cationically polymerizable compound (W12) at 25° C. is preferably within a range of 10 to 300 mPa·s. In this case, an increase in the viscosity of the composition (X) can be suppressed.
[0167] The cationically polymerizable functional group possessed by the polyfunctional cationically polymerizable compound (W12) is, for example, at least one group selected from the group consisting of an epoxy group, an oxetanyl group, and a vinyl ether group.
[0168] The siloxane skeleton possessed by the multifunctional cationic polymerizable compound (W12) may be linear, branched, or cyclic. The number of Si atoms possessed by the siloxane skeleton is preferably in the range of 2 to 14. In this case, the composition (X) can have a particularly low viscosity. The number of Si atoms is more preferably in the range of 2 to 10, further preferably in the range of 2 to 7, and particularly preferably in the range of 3 to 6.
[0169] The polyfunctional cationically polymerizable compound (W12) contains, for example, at least one of the compound represented by the formula (10) and the compound represented by the formula (11).
[0170]
Chemical formula 17
[0171]
[0172]
Chemical formula 18
[0173]
[0174] R in each of formula (10) and formula (11) is a single bond or a divalent organic group, preferably an alkylene group. Y is a siloxane skeleton, which may be any of a linear, branched, and cyclic structure, and the number of Si atoms is preferably in the range of 2 to 14, more preferably in the range of 2 to 10, further preferably in the range of 2 to 7, and particularly preferably in the range of 3 to 6. n is an integer greater than 2, preferably in the range of 2 to 4.
[0175] More specifically, for example, the polyfunctional cationically polymerizable compound (W12) contains a compound represented by the following formula (10a).
[0176]
Chemical formula 19
[0177]
[0178] R in formula (10a) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10a) is an integer greater than 0. n is preferably in the range of 0 to 12, more preferably in the range of 0 to 8, further preferably in the range of 0 to 5, and particularly preferably in the range of 1 to 4.
[0179] The compound represented by the formula (10a) preferably contains a compound represented by the following formula (30). That is, the polyfunctional cationically polymerizable compound (W12) preferably contains a compound represented by the following formula (30).
[0180] More specifically, the polyfunctional cationic polymerizable compound (W12) preferably contains at least one component selected from product numbers X-40-2669, X-40-2670, X-40-2715, X-40-2732, X-22-169AS, X-22-169B, X-22-2046, X-22-343, X-22-163 and X-22-163B manufactured by Shin-Etsu Chemical Co., Ltd.
[0181] It is preferred that the polyfunctional cationic polymerizable compound (W12) has an alicyclic epoxy structure, and it is particularly preferred that the polyfunctional cationic polymerizable compound (W12) contains a compound represented by formula (10a). The compound represented by formula (10a) can be particularly helpful in improving the cationic polymerization reactivity and reducing the viscosity of the composition (X), and can be particularly helpful in improving the heat discoloration resistance and low elastic modulus of the cured product and optical components. When the composition (X) contains a hygroscopic agent (E), it can also be particularly helpful in improving the dispersibility of the hygroscopic agent (E) in the composition (X).
[0182] When the composition (X) contains a polyfunctional cationically polymerizable compound (W12), the ratio of the polyfunctional cationically polymerizable compound (W12) to the total amount of the resin component is preferably in the range of 5 to 95% by mass. In this case, in particular, if the composition (X) contains a hygroscopic agent (E), the dispersibility of the hygroscopic agent (E) in the composition (X) and in the cured product is particularly improved, and the composition (X) can have a particularly high photocationic polymerization reactivity.
[0183] The monofunctional cationically polymerizable compound (W2) has only one cationically polymerizable functional group per molecule. The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetanyl group, and a vinyl ether group.
[0184] The viscosity of the monofunctional cationically polymerizable compound (W2) at 25°C is preferably 8 mPa·s or less. In this case, even if the composition (X) does not contain a solvent, the monofunctional cationically polymerizable compound (W2) can reduce the viscosity of the composition (X). In particular, the viscosity of the monofunctional cationically polymerizable compound (W2) at 25°C is preferably in the range of 0.1 to 8 mPa·s.
[0185] The monofunctional cationically polymerizable compound (W2) may contain, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (12) to (17) and limonene oxide.
[0186]
Chemical formula 20
[0187]
[0188]
Chemical formula 21
[0189]
[0190]
Chemical formula 22
[0191]
[0192]
Chemical formula 23
[0193]
[0194]
Chemical formula 24
[0195]
[0196]
Chemical formula 25
[0197]
[0198] The ratio of the monofunctional cationically polymerizable compound (W2) to the total amount of the resin component is preferably in the range of 5 to 50% by mass. If the ratio of the monofunctional cationically polymerizable compound (W2) is 5% by mass or more, the viscosity of the composition (X) can be particularly reduced. In addition, if the ratio of the monofunctional cationically polymerizable compound (W2) is 50% by mass or less, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and thereby the cured product can have high strength (hardness). The ratio of the monofunctional cationically polymerizable compound (W2) is more preferably 10% by mass or more, and further preferably 15% by mass or more. In addition, the ratio of the monofunctional cationically polymerizable compound (W2) is more preferably 40% by mass or less, further preferably 35% by mass or less, and particularly preferably 30% by mass or less. In particular, if the ratio of the monofunctional cationically polymerizable compound (W2) is 35% by mass or less, the volatilization amount of the components in the composition (X) during the storage of the composition (X) can be effectively reduced, and therefore, even if the composition (X) is stored for a long time, the characteristics of the composition (X) are not easily damaged. In addition, the generation of tackiness in the cured product can be particularly suppressed. For example, the ratio of the monofunctional cationically polymerizable compound (W2) is preferably within a range of 10 to 35% by mass.
[0199] In addition, particularly when the composition (X) contains a polyfunctional cationic polymerizable compound (W11) and a polyfunctional cationic polymerizable compound (W12), relative to the total amount of the resin component, the ratio of the polyfunctional cationic polymerizable compound (W11) is preferably in the range of 30 to 60% by mass, the ratio of the polyfunctional cationic polymerizable compound (W12) is in the range of 15 to 30% by mass, and the ratio of the monofunctional cationic polymerizable compound (W2) is in the range of 15 to 40% by mass. In this case, the good storage stability, low viscosity and good cationic polymerization reactivity of the composition (X) can be achieved in a balanced manner, and the excellent transparency, excellent hygroscopicity and high refractive index of the cured product can be achieved in a balanced manner.
[0200] If the cationic polymerizable compound (A2) contains a compound represented by formula (3) and a compound represented by formula (16), by adjusting the ratio of the two, the ease of the curing reaction when preparing a photocured material from the composition (X) can be adjusted to a moderate level, thereby achieving a low viscosity and improved storage stability of the composition (X).
[0201] The amount of the compound represented by formula (16) is appropriately adjusted so that the composition (X) has the above-mentioned properties. For example, the amount of the compound represented by formula (16) is preferably 10% by mass or more and 40% by mass or less based on the total amount of the resin component.
[0202] The cationically polymerizable compound (A2) preferably contains a compound (f1) represented by the following formula (30) (hereinafter also referred to as an aromatic epoxy compound (f1)).
[0203]
Chemical formula 26
[0204]
[0205] In formula (30), X is at least one selected from halogen, H, hydrocarbon group and alkylene glycol group. When there are multiple X in one molecule, they may be the same or different. The hydrocarbon group is, for example, an alkyl group or an aryl group. When X is a hydrocarbon group, the number of carbon atoms of X is, for example, in the range of 1 to 10. R is a single bond or a divalent organic group. When R is a divalent organic group, the divalent organic group is, for example, an alkylene group, an oxyalkylene group, a carbonyloxyalkylene group (for example, -CO-O-CH2-), or a -C(Ph)2-O-CH2- group. Y is H or a monovalent organic group. When Y is a monovalent organic group, the monovalent organic group is, for example, an alkyl group or an aryl group.
[0206] If the cationic polymerizable compound (A2) contains an aromatic epoxy compound (f1), the aromatic epoxy compound (f1) has a low viscosity, so the aromatic epoxy compound (f1) can easily reduce the viscosity of the composition (X). In addition, the aromatic epoxy compound (f1) is not easy to volatilize, so even if the composition (X) is stored, the composition (X) is not easy to change in composition due to the volatilization of the aromatic epoxy compound (f1). Therefore, the aromatic epoxy compound (f1) can easily improve the storage stability of the composition (X). In addition, the aromatic epoxy compound (f1) has high reactivity, so it is not easy for unreacted components to remain in the cured product, and it is not easy for escaping gas to be generated from the cured product. In addition, the aromatic epoxy compound (f1) can easily increase the glass transition temperature of the cured product, so it is easy to improve the heat resistance of the cured product.
[0207] In addition, the aromatic epoxy compound (f1) is less likely to generate defective droplets called splashing when the composition (X) is discharged by an inkjet method.
[0208] R in formula (30) is preferably a single bond or an alkylene group. When n in formula (30) is 2 or 3, it is preferred that at least one of the multiple Rs in formula (30) is a single bond or an alkylene group. In these cases, the reactivity of the aromatic epoxy compound (f1) tends to increase, and therefore the curability of the composition (X) when the composition (X) is irradiated with ultraviolet rays tends to increase.
[0209] The aromatic epoxy compound (f1) preferably contains at least one compound selected from the group consisting of compounds represented by the following formulae (301) to (318), for example.
[0210]
Chemical formula 27
[0211]
[0212] It is particularly preferred that the aromatic epoxy compound (f1) contains at least one component selected from the compounds represented by formulae (301) to (305), (312), (314) and (318). These compounds are likely to have high reactivity because at least one epoxy group (ethylene oxide) in the compound is bonded to a benzene ring via a single bond or an alkylene group, and thus are likely to improve the curability of the composition (X).
[0213] The ratio of the aromatic epoxy compound (f1) to the total cationic polymerizable compound (A2) is preferably 5% by mass or more. In this case, it is particularly easy to obtain the above-mentioned effect brought about by the aromatic epoxy compound (f1). The ratio is also preferably 95% by mass or less. In this case, the storage property of the composition (X) is easy to become good. The ratio is more preferably 10% by mass or more and 90% by mass or less, and further preferably 20% by mass or more and 85% by mass or less.
[0214] It is also preferred that the cationically polymerizable compound (A2) contains a compound (f2) having an oxyalkylene skeleton. The oxyalkylene skeleton refers to a linear skeleton containing one or more linear oxyalkylene units.
[0215] If the cationic polymerizable compound (A2) contains the compound (f2), the compound (f2) has a low viscosity, so the compound (f2) can easily reduce the viscosity of the composition (X). In addition, the compound (f2) is not easy to volatilize, so even if the composition (X) is stored, the composition (X) is not easy to change in composition due to the volatilization of the aromatic epoxy compound (f1). Therefore, the compound (f2) can easily improve the storage stability of the composition (X).
[0216] In addition, compound (f2) makes it difficult to produce bad droplets called splashing when the composition (X) is ejected by inkjet method. In addition, even if the speed of the droplets ejected by inkjet method is increased, compound (f2) can also make it difficult to produce splashing. Therefore, although it also depends on the conditions of inkjet, for example, the ejection speed of the droplets based on the inkjet method can be set to 4m / s or more without splashing. If the speed of the droplets can be increased, the trajectory of the droplets is not easily affected by external interference, so the dimensional accuracy of the solidified material made by the composition (X) can be improved. In addition, as described above, since compound (f2) can improve the storage stability of the composition (X), even if the composition (X) is kept for a long time, it is easy to maintain the characteristic of the composition (X) that is not easy to produce splashing.
[0217] The oxyalkylene skeleton particularly preferably contains the structure of "-CCO-", i.e., an oxymethylene unit. In this case, splashing is particularly difficult to occur, for example, even if the driving frequency when the composition (X) is ejected by the inkjet method is changed, splashing is not easy to occur. In addition, the compound (f2) is less volatile and can easily achieve a lower viscosity, and the affinity (wettability) of the composition (X) for inorganic materials is easily improved.
[0218] The number of oxyalkylene units in the oxyalkylene skeleton in the compound (f2) is preferably 1 to 8. In this case, the compound (f2) easily reaches a lower viscosity, and therefore, splashing is particularly difficult to occur, and the crosslinking density of the cured product is easily increased, so the glass transition temperature of the cured product is particularly easy to increase. The number of the oxyalkylene units is more preferably 1 to 6, and further preferably 1 to 4.
[0219] It should be noted that a substituent other than hydrogen may be bonded to the oxyalkylene unit in the oxyalkylene skeleton in the compound (f2). For example, the oxymethylene unit contained in the oxyalkylene skeleton may have a structure of "-CH(CH3)-CH2-O-".
[0220] The ratio of compound (f2) is preferably 10% by mass or more relative to the cationic polymerizable compound (A2). In this case, the inkjet property becomes good and the wettability to the substrate becomes better. The ratio is also preferably 70% by weight or less. In this case, the glass transition temperature can be fully increased. The ratio is more preferably 15% by mass or more and 60% by mass or less, and further preferably 20% by mass or more and 50% by mass or less.
[0221] The compound (f2) contains, for example, at least one of a compound (f21) having an oxyalkylene skeleton and an epoxy group and a compound (f22) having an oxyalkylene group and an oxetane group.
[0222] Compound (f21) contains, for example, at least one compound selected from the group consisting of the compound represented by formula (1b), the compound represented by formula (4), the compound represented by formula (5), the compound represented by formula (6), the compound represented by formula (7), the compound represented by formula (8), the compound represented by formula (13), the compound represented by formula (14), etc. It should be noted that the components that compound (f21) may contain are not limited to the above components.
[0223] Compound (f22) contains, for example, at least one compound selected from the group consisting of the compound represented by formula (3), the compound represented by formula (12), the compound represented by formula (16), and the compound represented by formula (17). It should be noted that the components that compound (f22) may contain are not limited to the above components.
[0224] The cationic polymerizable compound (A2) also preferably contains an epoxy compound and the above-mentioned compound (f22). The epoxy compound, for example, contains at least one compound having an epoxy group among the compounds that can be included in the above-mentioned cationic polymerizable compound (A2). If the cationic polymerizable compound (A2) contains an epoxy compound and a compound (f22), the curability of the composition (X) when the composition (X) is irradiated with ultraviolet rays is easily improved, and the composition (X) at this time is not easy to cause too intense curing, so the cured product is not easy to produce a deterioration in transparency caused by white turbidity, etc. It is speculated that the mechanism of this effect is as follows. The reactivity of the compound (f22) is lower than that of the epoxy compound, so if the composition (X) is irradiated with ultraviolet rays, the epoxy compound reacts first. Through the reaction of the epoxy compound, the curability of the composition (X) tends to become higher. Next, the compound (f22) reacts, thereby making it difficult for the epoxy compound to react with the compound (f22). It can be considered that it is not easy to cause an overly intense reaction. At this time, the ratio of compound (f22) to cationic polymerizable compound (A2) is preferably 20% by mass or more. In this case, it is particularly easy to make the composition (X) low-viscosity by compound (f22), and it is particularly easy to improve the storage stability of composition (X). In addition, it is particularly easy to improve the curability of composition (X) by compound (f22). The ratio of compound (f22) is also preferably 90% by mass or less. In this case, the curability of the cured product can be fully improved. The ratio of compound (f22) is more preferably 10% by mass or more and 90% by mass or less, and further preferably 20% by mass or more and 80% by mass or less. In addition, the ratio of epoxy compound at this time is preferably 10% by mass or more and 90% by mass or less relative to the total amount of cationic polymerizable compound (A2), more preferably 20% by mass or more and 80% by mass or less, and further preferably 25% by mass or more and 75% by mass or less. In these cases, the unreacted groups in the cured product can be fully reduced, and the curability of the cured product can be fully improved.
[0225] The epoxy compound preferably contains a compound having at least one oxirane ring that does not constitute a glycidyl ether group. In this case, the epoxy compound is particularly likely to improve the curability of the composition (X). It is more preferred if the epoxy compound contains a compound having two or more oxirane rings that do not constitute a glycidyl ether group. The epoxy compound also preferably contains a compound that does not have a glycidyl ether group. It is particularly preferred if the epoxy compound contains a compound having two or more oxirane rings that do not constitute a glycidyl ether group and does not have a glycidyl ether group.
[0226] It is particularly preferred if the cationic polymerizable compound (A2) contains a compound (f2) and an epoxy compound, and furthermore, the epoxy compound contains the above-mentioned aromatic epoxy compound (f1). In this case, the composition (X) is likely to have particularly excellent storage stability, and in addition, when the composition (X) is ejected by an inkjet method, it is particularly difficult to produce undesirable droplets known as splashes. In addition, even if the speed of the droplets ejected by the inkjet method is increased, splashes can be particularly difficult to produce. In addition, even if the composition (X) is stored for a long time, it is particularly easy to maintain the characteristic of the composition (X) that splashes are not easy to produce. In this case, it is particularly preferred that the compound (f2) contains a compound (f22).
[0227] The total ratio of the aromatic epoxy compound (f1) and the compound (f22) to the cationic polymerizable compound (A2) is preferably 55% by mass or more. In this case, the effect brought about by the combination of the aromatic epoxy compound (f1) and the compound (f22) is particularly significantly obtained. The ratio is more preferably 60% by mass or more, and further preferably 70% by mass or more. It is particularly preferred that the cationic polymerizable compound (A2) contains only the aromatic epoxy compound (f1) and the compound (f22).
[0228] From the viewpoint of reactivity, the cationic polymerizable compound (A2) is preferably an alicyclic epoxy. Specifically, the cationic polymerizable compound (A2) contains at least one selected from the group consisting of a compound represented by formula (20a) (e.g., product number THI-DE manufactured by JX Energy Co., Ltd.), a compound represented by formula (1a) (e.g., trade name CELLOXIDE 8010 manufactured by Daicel), a compound represented by formula (1b) (e.g., trade name CELLOXIDE 2021P manufactured by Daicel), and limonene dioxide (e.g., LDO manufactured by Arkema). The percentage of the cationic polymerizable compound (A2) relative to the total cationic polymerizable compound (A) is preferably 40% by mass or more.
[0229] The photocationic polymerization initiator (B2) is not particularly limited as long as it is a catalyst that generates a protonic acid or a Lewis acid upon exposure to light. The photocationic polymerization initiator (B2) may contain at least one of an ionic photoacid generating type cationic curing catalyst and a nonionic photoacid generating type cationic curing catalyst.
[0230] The ionic photoacid generating type cationic curing catalyst may contain at least one of an onium salt and an organic metal complex. Examples of onium salts include aromatic diazonium salts, aromatic halogen onium salts, and aromatic sulfonium salts. Examples of organic metal complexes include iron-arene complexes, titanocene complexes, and arylsilanol-aluminum complexes. The ionic photoacid generating type cationic curing catalyst may contain at least one of these components.
[0231] The nonionic photoacid generating type cationic curing catalyst may contain, for example, at least one component selected from nitrobenzyl ester, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonates, naphthoquinone diazo and N-hydroxyimide phosphonates. It should be noted that the components that the nonionic photoacid generating type cationic curing catalyst may contain are not limited to the above components.
[0232] More specific examples of the compound that the photocationic polymerization initiator (B2) can contain include: DPI series (105, 106, 109, 201, etc.), BI-105, MPI series (103, 105, 106, 109, etc.), BBI series (101, 102, 103, 105, 106, 109, 110, 200, 210, 300, 301, etc.) manufactured by Midori Kagaku TSP series (102, 103, 105, 106, 109, 200, 300, 1000, etc.), HDS-109, MDS series (103, 105, 109, 203, 205, 209, etc.), BDS-109, MNPS-109, DTS series (102, 103, 105, 200, etc.), NDS series (103, 105, 155, 165, etc.), DAM series ( 101, 102, 103, 105, 201, etc.), SI series (105, 106, etc.), PI-106, NDI series (105, 106, 109, 1001, 1004, etc.), PAI series (01, 101, 106, 1001, 1002, 1003, 1004, etc.), MBZ-101, PYR-100, NB series (101, 201, etc.), NAI series (10 0, 1002, 1003, 1004, 101, 105, 106, 109, etc.), TAZ series (100, 101, 102, 103, 104, 107, 108, 109, 110, 113, 114, 118, 122, 123, 203, 204, etc.), NBC-101, ANC-101, TPS-Acetate, DTS-Acetate, Di-Boc Bisphinol A, tert-Butyl lithocholate, tert-Butyl deoxycholate, tert-Butyl cholate, BX, BC-2, MPI-103, BDS-105, TPS-103, NAT-103, BMS-105 and TMS-105;
[0233] CYRACURE UVI-6970, CYRACURE UVI-6974, CYRACURE UVI-6990 and CYRACURE UVI-950 manufactured by Union Carbide, USA;
[0234] Irgacure 250, Irgacure 261 and Irgacure 264 manufactured by BASF;
[0235] CG-24-61 manufactured by CIBA-GEIGYAG;
[0236] ADEKA OPTOMER SP-150, ADEKA OPTOMER SP-151, ADEKA OPTOMER SP-170 and ADEKA OPTOMER SP-171 manufactured by ADEKA Co., Ltd.;
[0237] DAICAT II manufactured by Daicel Co., Ltd.;
[0238] UVAC 1590 and UVAC 1591 manufactured by Daicel Cytech Co., Ltd.
[0239] CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758 and CIT-1682 manufactured by Nippon Soda Co., Ltd.;
[0240] Tetrakis(pentafluorophenyl)borate toluoylcumyliodonium salt, i.e., PI-2074, manufactured by RHODIA;
[0241] FFC509 made by 3M;
[0242] CD-1010, CD-1011 and CD-1012 made by Sartomer of the United States;
[0243] CPI-100P, CPI-101A, CPI-110P, CPI-110A and CPI-210S manufactured by San-Apro Co., Ltd.; and
[0244] UVI-6992 and UVI-6976 manufactured by Dow Chemical Co. The photocationic polymerization initiator (B2) may contain at least one compound selected from these compounds.
[0245] The ratio of the photocationic polymerization initiator (B2) to the cationic polymerizable compound (A2) is preferably in the range of 1 to 4 mass %. By making the ratio 1 mass % or more, the composition (X) can have particularly good cationic polymerization reactivity. In addition, by making the ratio 4 mass % or less, the composition (X) can have good storage stability, and the manufacturing cost can be reduced by not containing an excessive amount of photocationic polymerization initiator (B2).
[0246] The composition (X) may contain a sensitizer (C). In this case, the sensitizer (C) can promote the reaction of the photopolymerization initiator (B), and thus the difference between the first cure shrinkage and the second cure shrinkage of the composition (X) can be easily reduced.
[0247] The sensitizer (C) may contain, for example, at least one compound selected from 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene, 9-hydroxymethylanthracene, thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, anthraquinone, 1,2-dihydroxyanthraquinone, 2-ethylanthraquinone, 1,4-diethoxynaphthalene, p-dimethylaminoacetophenone, p-diethylaminoacetophenone, p-dimethylaminobenzophenone, p-diethylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, p-dimethylaminobenzaldehyde, and p-diethylaminobenzaldehyde. It should be noted that the components that the sensitizer (C) may contain are not limited to the above components.
[0248] The sensitizer (C) preferably contains at least one of an anthracene compound and an anthraquinone compound. The anthracene compound, for example, contains at least one selected from 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene and 9-hydroxymethylanthracene. The thioxanthone compound, for example, contains at least one selected from thioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2-chlorothioxanthone and 2,4-diethylthioxanthone.
[0249] The sensitizer (C) particularly preferably contains an anthracene compound. In this case, the transparency of the composition (X) is less likely to be impaired, so the coating of the composition (X) is easily cured uniformly from the surface layer to the deep part, and therefore the cured product is particularly less likely to have unevenness.
[0250] The percentage of sensitizer (C) relative to composition (X) is preferably 0.05% by mass or more. In this case, the reactivity of composition (X) is particularly easy to become high, so the difference between the first cure shrinkage and the second cure shrinkage is particularly easy to become small. This percentage is more preferably 0.1% by mass or more, and more preferably 0.3% by mass or more. In addition, the percentage of sensitizer (C) is preferably 2.0% by mass or less. In this case, the coating of composition (X) is easily cured uniformly from the surface layer to the deep part, so the cured product is particularly difficult to produce concavoconvex. This percentage is more preferably 1.5% by mass or less, and more preferably 1.0% by mass or less.
[0251] The composition (X) may contain a leveling agent (D). The leveling agent (D) makes it easy to smooth the surface of the coating film of the composition (X). Therefore, when the coating film is irradiated with ultraviolet rays, the coating film is easy to cure uniformly, and therefore, the cured product is particularly difficult to produce unevenness.
[0252] Leveling agent (D) preferably contains silane compound (D1). Silane compound (D1) preferably contains silane compound (D11) with nitrogen atom and alkoxysilyl group. In this case, the affinity of composition (X) and cured product with inorganic materials such as silicon nitride is improved, so the smoothness of coating and cured film is particularly easy to improve. Silane compound (D11) particularly preferably contains silane compound (D12) with azacyclopentane skeleton (pyrrolidine skeleton). In this case, the smoothness of coating and cured film is particularly easy to improve. Silane compound (D12) for example has an alkoxy group bonded to Si in azacyclopentane skeleton, and a structure in which organic groups such as hydrocarbon groups are bonded to nitrogen in azacyclopentane skeleton. Hydrocarbon groups are for example aryl, alkyl, alkenyl or alkynyl.
[0253] The silane compound (D12) preferably contains azasilacyclopentane silane. Azasilacyclopentane silane has, for example, a structure represented by the following formula (4).
[0254]
Chemical formula 28
[0255]
[0256] In formula (4), R 1 and R 2 X is an organic group, for example, a hydrocarbon group.
[0257] R 1 and R 2 The number of carbon atoms of each is preferably 1 or more and 5 or less, more preferably 1 or more and 3 or less, and further preferably 1 or more and 2 or less.
[0258] When X is a hydrocarbon group, the hydrocarbon group is, for example, an aryl group, an alkyl group, an alkenyl group, or an alkynyl group. The number of carbon atoms in the hydrocarbon group is preferably 3 or more and 20 or less, more preferably 4 or more and 17 or less, and further preferably 6 or more and 14 or less. Specifically, the hydrocarbon group is, for example, a linear alkyl group such as methyl, ethyl, propyl, butyl, hexyl, decyl, octyl, tetradecyl, etc.; a branched alkyl group such as isopropyl, tert-butyl, isobutyl, etc.; a cyclic alkyl group such as cyclohexyl; an aryl group such as phenyl, tolyl, xylyl, etc.; an aralkyl group such as phenethyl or diphenylmethyl.
[0259] The silane compound (D11) contains, for example, at least one selected from 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-octyl-1-aza-2-silacyclopentane and 2,2-dimethoxy-1-tetradecyl-1-aza-2-silacyclopentane.
[0260] The compounds that the silane compound (D1) may contain are not limited to the above-mentioned silane compound (D11). The silane compound (D1) may contain a suitable organic alkoxysilane, for example, the silane compound (D1) may contain at least one compound selected from N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, and hexyltrimethoxysilane.
[0261] In addition, the compound that the leveling agent (D) may contain is not limited to the silane compound (D1). For example, the leveling agent (D) may contain at least one compound selected from the group consisting of fluorine compounds, acrylic copolymers, and alcohol alkoxylate compounds.
[0262] The percentage of the leveling agent (D) relative to the composition (X) is preferably 0.1% by mass or more. In this case, the cured product is less likely to have unevenness. The percentage is more preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. In addition, the percentage of the leveling agent (D) is preferably 3.0% by mass or less. In this case, there is an advantage of being able to prevent excessive reduction in surface tension and causing deterioration in inkjet ejection properties. The percentage is more preferably 2.5% by mass or less, and more preferably 2.0% by mass or less.
[0263] The composition (X) may further contain a hygroscopic agent (E). If the composition (X) contains a hygroscopic agent (E), the cured product of the composition (X) and the sealing material 5 may have hygroscopicity. Therefore, the sealing material 5 can make it more difficult for moisture to invade the light-emitting element 4 in the light-emitting device 1. The average particle size of the hygroscopic agent (E) is preferably less than 200 nm. In this case, the cured product may have high transparency.
[0264] The moisture absorbent (E) is preferably hygroscopic inorganic particles, and preferably contains at least one component selected from zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. In particular, the moisture absorbent (E) preferably contains zeolite particles.
[0265] The zeolite particles with an average particle size of less than 200 nm can be manufactured, for example, by crushing conventional industrial zeolites. When manufacturing the zeolite particles, the zeolite can be crystallized by hydrothermal synthesis after being crushed, in which case the zeolite particles can have particularly high hygroscopicity. Examples of methods for manufacturing such zeolite particles are disclosed in Japanese Patent Publication No. 2016-69266, Japanese Patent Publication No. 2013-049602, etc.
[0266] When the composition (X) contains a hygroscopic agent (E), the ratio of the hygroscopic agent (E) relative to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the ratio of the hygroscopic agent (E) is 1% by mass or more, the cured product can have a particularly high hygroscopicity. In addition, if the ratio of the hygroscopic agent (E) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can have a sufficiently low viscosity to the extent that it can be applied by an inkjet method. The ratio of the hygroscopic agent (E) is further preferably 3% by mass or more, particularly preferably 5% by mass or more. In addition, the ratio of the hygroscopic agent (E) is more preferably 15% by mass or less, particularly preferably 13% by mass or less.
[0267] The composition (X) may further contain inorganic fillers other than the hygroscopic agent (E). In particular, the composition (X) preferably contains nano-sized high refractive index particles. Examples of high refractive index particles include zirconium oxide particles. If the composition (X) contains high refractive index particles, the refractive index of the cured product can be increased while maintaining the good transparency of the cured product. Therefore, when the cured product is applied to the sealing material 5 in the light-emitting device 1, the efficiency of extracting light emitted to the outside through the sealing material 5 can be improved. The average particle size of the high refractive index particles is preferably in the range of 5 to 30 nm, and more preferably in the range of 10 to 20 nm.
[0268] The proportion of high refractive index particles in the composition (X) is appropriately designed so that the cured product has a desired refractive index. It is particularly preferred that high refractive index particles are contained in the composition (X) so that the refractive index of the cured product is within a range of 1.45 or more and less than 1.55. In this case, the light extraction efficiency of the light emitting device 1 is particularly improved.
[0269] When the composition (X) contains a hygroscopic agent (E), it is preferred that the composition (X) further contains a dispersant (F). In this case, the dispersant (F) can improve the dispersibility of the hygroscopic agent (E) in the composition (X). Therefore, in the composition (X), an increase in viscosity and a decrease in storage stability due to the hygroscopic agent (E) are less likely to occur.
[0270] The structure of the light emitting device 1 is described. The light emitting device 1 includes a light source and an optical component that transmits light emitted by the light source. For example, the light emitting device 1 includes a light emitting element 4, a sealing material 5 covering the light emitting element 4, and a passivation layer 6. In this case, the light emitting element 4 is a light source, the sealing material 5 is an optical component, and the passivation layer 6 is an inorganic layer. The sealing material 5 and the passivation layer 6 overlap.
[0271] The light emitting element 4 includes, for example, a light emitting diode. The light emitting diode includes, for example, at least one of an organic EL element (organic light emitting diode) and a micro light emitting diode. When the light emitting element 4 includes an organic light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, an organic EL display. When the light emitting element 4 includes a micro light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, a micro LED display. It should be noted that EL is an abbreviation for electroluminescence.
[0272] Reference Figure 1 An example of the structure of a light emitting device 1 is described. The light emitting device 1 is a top emission type. The light emitting device 1 includes a supporting substrate 2, a transparent substrate 3 opposed to the supporting substrate 2 with a gap therebetween, a light emitting element 4 located on the surface of the supporting substrate 2 opposed to the transparent substrate 3, and a passivation layer 6 and a sealing material 5 covering the light emitting element 4.
[0273] The support substrate 2 is made of, for example, a resin material, but is not limited thereto. The transparent substrate 3 is made of a light-transmitting material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. The light-emitting element 4 includes, for example, a pair of electrodes 41, 43 and an organic light-emitting layer 42 located between the electrodes 41, 43. The organic light-emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light-emitting layer 423 and an electron transport layer 424, and these layers are stacked in the above order.
[0274] The light-emitting device 1 includes a plurality of light-emitting elements 4, and the plurality of light-emitting elements 4 form an array 9 (hereinafter referred to as the element array 9) on the supporting substrate 2. The element array 9 also includes a partition wall 7. The partition wall 7 is located on the supporting substrate 2 and separates two adjacent light-emitting elements 4. The partition wall 7 is made, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes a connection wiring 8 that electrically connects the electrodes 43 of the adjacent light-emitting elements 4 and the electron transport layer 424 to each other. The connection wiring 8 is provided on the partition wall 7.
[0275] The passivation layer 6 is preferably made of silicon nitride or silicon oxide, and is particularly preferably made of silicon nitride. Figure 1 In the example shown, the passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state of being in direct contact with the element array 9, thereby covering the light emitting element 4. The second passivation layer 62 is arranged at a position opposite to the element array 9 relative to the first passivation layer 61, and a gap is provided between the second passivation layer 62 and the first passivation layer 61. The sealing material 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is interposed between the light emitting element 4 and the sealing material 5 covering the light emitting element 4.
[0276] In addition, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. The material of the second sealing material 52 is not particularly limited. The material of the second sealing material 52 can be the same as or different from that of the sealing material 5.
[0277] A method for producing the sealing material 5 and a method for producing the light-emitting device 1 using the composition (X) will be described.
[0278] In this embodiment, it is preferred that after the composition (X) is formed by an inkjet method, ultraviolet rays are irradiated on the composition (X) to cure it, thereby producing the sealing material 5. In this embodiment, the composition (X) can be formed by applying it by an inkjet method.
[0279] When the composition (X) is applied by an inkjet method, if the composition (X) has a sufficiently low viscosity at room temperature, for example, a viscosity at 25°C of 30 mPa·s or less, particularly 15 mPa·s or less, the composition (X) can be applied by an inkjet method to form a film without heating the composition (X).
[0280] When the composition (X) has a property of decreasing viscosity by heating, the composition (X) can be heated and then applied by an inkjet method to form the composition (X). When the viscosity of the composition (X) at 40°C is 30 mPa·s or less, particularly 15 mPa·s or less, the viscosity of the composition (X) can be decreased by simply heating the composition (X), and the decreased viscosity composition (X) can be ejected by an inkjet method. The heating temperature of the composition (X) is, for example, 20°C or more and 50°C or less.
[0281] More specifically, for example, a support substrate 2 is first prepared. For example, a photosensitive resin material is used to form a partition wall 7 on one side of the support substrate 2 by photolithography. Next, a plurality of light-emitting elements 4 are provided on one side of the support substrate 2. The light-emitting element 4 can be produced by an appropriate method such as a vapor deposition method or a coating method. In particular, it is preferred to produce the light-emitting element 4 by a coating method such as an inkjet method. Thus, an element array 9 is produced on the support substrate 2.
[0282] Next, the first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by, for example, a vapor deposition method such as a plasma CVD method.
[0283] Next, the composition (X) is formed on the first passivation layer 61 by, for example, an inkjet method to form a coating film. If the inkjet method is applied to both the formation of the light-emitting element 4 and the coating of the composition (X), the manufacturing efficiency of the light-emitting device 1 can be particularly improved. Next, the coating film of the composition (X) is cured by irradiating ultraviolet rays to form a sealing material 5. The thickness of the sealing material 5 is, for example, 5 μm or more and 50 μm or less.
[0284] When irradiating the composition (X) with ultraviolet rays, the composition (X) may be irradiated with ultraviolet rays in an oxygen-containing atmosphere such as an air atmosphere, or may be irradiated with ultraviolet rays in an inert atmosphere such as a nitrogen atmosphere. In the present embodiment, as described above, since the oxygen ratio of the composition (X) is 75% by mass or less, oxygen hindrance is not likely to occur, especially even if the photopolymerizable compound (A) contains a free radical polymerizable compound (A1). Therefore, even if the composition (X) is irradiated with ultraviolet rays in an oxygen-containing atmosphere, the composition (X) is easily cured.
[0285] Next, the second passivation layer 62 is provided on the sealing material 5. The second passivation layer 62 can be formed by, for example, a vapor deposition method such as a plasma CVD method.
[0286] Next, after an ultraviolet curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, the transparent substrate 3 is stacked on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.
[0287] Next, ultraviolet rays are irradiated from the outside to the transparent substrate 3. The ultraviolet rays pass through the transparent substrate 3 and reach the ultraviolet curable resin material. As a result, the ultraviolet curable resin material is cured, and the second sealing material 52 is produced.
[0288] In the present embodiment, as described above, it is possible to prevent a decrease in light emission efficiency due to the passivation layer 6 and the sealing material 5 in the light emitting device 1 from occurring.
[0289] The thickness of the sealing material 5 is, for example, not less than 1 μm and not more than 20 μm. The thickness of the sealing material 5 may be not more than 15 μm. In this case, the light-emitting device 1 can be made thinner by making the sealing material 5 lighter and thinner, and a flexible light-emitting device 1 can be obtained. In addition, even if the thickness of the sealing material 5 is not more than 10 μm, in the present embodiment, it is difficult to produce a reduction in luminous efficiency caused by the passivation layer 6 and the sealing material 5 in the light-emitting device 1. The thickness of the sealing material 5 is more preferably not more than 8 μm. In addition, in order to effectively suppress moisture from reaching the light-emitting element 4 through the sealing material 5, the thickness of the sealing material 5 is preferably not less than 3 μm, and more preferably not less than 5 μm.
[0290] The thickness of the passivation layer 6 overlapping the sealing material 5 is, for example, 0.1 μm to 2 μm. When the passivation layer 6 includes the first passivation layer 61 and the second passivation layer 62 as described above, the thickness of each of the first passivation layer 61 and the second passivation layer 62 is preferably 0.1 μm to 2 μm.
[0291] It should be noted that the use of the composition (X) of this embodiment is not limited to the preparation of the sealing material 5 for the light-emitting element 4. The composition (X) can be used to make various optical components that allow the light emitted by the light source to pass through. For example, the optical component can be a color resist. That is, for example, the composition (X) can contain a phosphor, and the color resist in the color filter can be made from the composition (X). The color filter can be set in a display device such as an organic EL display or a micro LED display as a light-emitting device.
[0292] [Example]
[0293] 1. Preparation of the composition
[0294] The compositions of Examples and Comparative Examples were prepared by mixing the components shown in the following table.
[0295] The viscosity of each component was measured using a rheometer (manufactured by Anton Paar Japan, model DHR-2) at a temperature of 25°C and a shear rate of 1000 s. -1 The value measured under the conditions of .
[0296] -Acryloylmorpholine, viscosity 12mPa·s.
[0297] -Morpholin-4-yl acrylate: viscosity 16 mPa·s.
[0298] - Polyethylene glycol 200 dimethacrylate: manufactured by Shin-Nakamura Chemical Industry Co., Ltd., viscosity 14 mPa·s.
[0299] -Tripropylene glycol diacrylate: viscosity 15 mPa·s.
[0300] -Pentaerythritol tetraacrylate: viscosity 350 mPa·s.
[0301] -Irgacure TPO: manufactured by BASF, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, absorption coefficient of light at a wavelength of 405 nm is 165 ml / g·cm, and has photobleaching properties.
[0302] - Irgacure 819: manufactured by BASF, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, absorption coefficient of light at a wavelength of 405 nm is 900 ml / g·cm, and has photobleaching properties.
[0303] - Irgacure 907: manufactured by BASF, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, absorption coefficient of light at a wavelength of 405 nm is 0 ml / g·cm, and has no photobleaching property.
[0304] - Irgacure 184: manufactured by BASF, 1-hydroxy-cyclohexyl-phenyl-ketone, absorption coefficient of light at a wavelength of 405 nm is 0 ml / g·em, no photobleaching property.
[0305] -Sensitizer 1: Anthracene-based sensitizer, manufactured by Kawasaki Chemical Industries, Ltd., trade name ANTHRACURE (registered trademark) UVS-581.
[0306] -Sensitizer 2: Thioxanthone-based sensitizer, 2,4-diethylthioxanthone, manufactured by Nippon Kayaku Co., Ltd., trade name KAYACURE DETX-S.
[0307] -Leveling agent 1: 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane.
[0308] -Leveling agent 2: 2,2-dimethoxy-1-tetradecyl-1-aza-2-silacyclopentane.
[0309] -Leveling agent 3: phenyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-103.
[0310] - Leveling agent 4: Hexyltriethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., trade name KBM-3063.
[0311] 2. Evaluation test
[0312] The following evaluation tests were carried out on the Examples and Comparative Examples, and the results are shown in the table.
[0313] (1) Viscosity
[0314] A rheometer (Anton Paar Japan, Model DHR-2) was used at a temperature of 25°C and a shear rate of 1000 s. -1 The viscosity of the composition was measured under the conditions of .
[0315] (2) Inkjet properties
[0316] The composition was added to an ink cartridge of an inkjet printer (manufactured by FUJIFILM, model DMP2831), and droplets of the composition were ejected from the nozzle of the inkjet printer at a temperature of 30° C. and a frequency of 1 kHz. The droplets were observed with a high-speed camera, and the case where neither ink mist nor splashing was confirmed was evaluated as “A”, and the case where at least one of ink mist and splashing was confirmed was evaluated as “B”.
[0317] (3) Transmittance
[0318] The composition was applied to form a coating film with a thickness of 10 μm, and an LED-UV irradiator (model E075IIHD, peak wavelength 395 nm) manufactured by Ushio Co., Ltd. was used to irradiate the film at 3 W / cm 2 The coating film was irradiated with ultraviolet rays at an irradiation intensity of 5.3 seconds and then heated at 100° C. for 5 minutes to prepare a film. The total light transmittance of the film was measured in accordance with JIS K7361-1.
[0319] (4) Response rate
[0320] The composition was measured using an infrared spectrometer (manufactured by Agilent Technologies, model Agilent Cary 610 FTIR microscope system) to obtain an IR spectrum.
[0321] The composition was applied to form a coating film with a thickness of 10 μm, and a UV irradiator (manufactured by CCS, model CKL-200) was used at an irradiation intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 The coating film was irradiated with ultraviolet rays having a peak wavelength of 395 nm under the conditions of . Next, the composition (cured product) after irradiation with ultraviolet rays was measured using the above-mentioned infrared spectrometer to obtain an IR spectrum.
[0322] In both IR spectra, the -1 The peak intensity of the absorption of the acryloyl group that appears. Based on the peak intensity I0 of the coating and the peak intensity I1 of the cured product, the reduction rate of the reactive functional group ((meth)acryloyl group) in the composition before and after ultraviolet irradiation is calculated using the formula {1-(I0-I1) / I0}×100(%). The result is taken as the reaction rate.
[0323] (5) Difference in shrinkage
[0324] The composition thickness was 10 μm, and the UV irradiator (manufactured by CCS, model CKL-200) was used with a peak wavelength of 395 nm and an irradiation intensity of 7 W / cm 2 And the accumulated light intensity is 2.1J / cm 2 The curing shrinkage of the ultraviolet curing resin according to JIS K6941 was measured under the conditions of , and the curing shrinkage of the composition was calculated.
[0325] Change the UV irradiation conditions to an irradiation intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 , the curing shrinkage of the composition was calculated in the same manner except for the above.
[0326] The absolute value of the difference between the two curing shrinkage ratios obtained above was calculated.
[0327] (6) Uneven stripes
[0328] The composition was applied to a quartz glass sheet (size 50 mm×25 mm×1 mm) on which a silicon oxynitride film (SiON film) was formed by plasma CVD to form a coating film with a thickness of 10 μm. The coating film was prepared in an atmosphere using a Unijet E075IIHD (peak wavelength 395 nm) manufactured by Ushio Electron at an irradiation intensity of 5 W / cm 2 , and the accumulated light intensity is 3000mJ / cm 2 The coating film is irradiated with ultraviolet rays under conditions of to cure it to obtain a cured film.
[0329] The surface of the cured film was visually observed, and the case where no streak-like unevenness was observed on the cured film was evaluated as "A", the case where streak-like unevenness was observed in an area less than 10% of the surface of the cured film was evaluated as "B", and the case where streak-like unevenness was observed in an area of 10% or more of the surface of the cured film was evaluated as "C".
[0330]
Table 1
[0331]
Claims
1. A UV-curable resin composition comprising a photopolymerizable compound A and a photopolymerization initiator B, The photopolymerizable compound A contains a radical polymerizable compound A1, The radical polymerizable compound A1 contains an acrylic compound Y, The acrylic compound Y contains a multifunctional acrylic compound Y1, wherein the multifunctional acrylic compound Y1 has two or more radical polymerizable functional groups including a (meth)acryloyl group in one molecule, The multifunctional acrylic compound Y1 contains tripropylene glycol diacrylate and pentaerythritol tetraacrylate, The ratio of the polyfunctional acrylic compound Y1 to the total acrylic compound Y is 50% by mass or more and 100% by mass or less, The photopolymerization initiator B is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, or 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, or 1-hydroxy-cyclohexyl-phenyl-ketone, The ultraviolet curable resin composition further contains a leveling agent D, The leveling agent D is 2,2-dimethoxy-1-phenyl-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-tetradecyl-1-aza-2-silacyclopentane, phenyltrimethoxysilane or hexyltriethoxysilane. The percentage of the leveling agent D relative to the ultraviolet curable resin composition is 0.1 mass % or more, A coating film with a thickness of 10 μm was prepared from the UV-curable resin composition and irradiated at an intensity of 7 W / cm 2 And the accumulated light intensity is 2.1J / cm 2 The curing shrinkage when the coating film is irradiated with ultraviolet light having a peak wavelength in any wavelength range of 385 nm to 405 nm under the conditions of irradiation intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 The absolute value of the difference in curing shrinkage when irradiated with the ultraviolet rays under the conditions of is 2 percentage points or less.
2. The ultraviolet curable resin composition according to claim 1, wherein A coating film with a thickness of 10 μm was prepared from the UV-curable resin composition and irradiated at an intensity of 3 W / cm 2 And the accumulated light intensity is 0.9J / cm 2 The reaction rate of the photopolymerizable compound A when the coating film is irradiated with ultraviolet light having a peak wavelength of 395 nm is 80% or more.
3. The ultraviolet curable resin composition according to claim 1 or 2, wherein The photopolymerization initiator B contains a photopolymerization initiator B3 having a photobleaching property, and the percentage of the photopolymerization initiator B3 relative to the photopolymerization initiator B is 50 mass % or more.
4. The ultraviolet curable resin composition according to claim 1 or 2, wherein The photopolymerization initiator B includes a photopolymerization initiator B4 having an extinction coefficient of light of a wavelength of 405 nm of 5 ml / g·cm or more, and the percentage of the photopolymerization initiator B4 relative to the photopolymerization initiator B is 50 mass % or more. 5 . The ultraviolet curable resin composition according to claim 1 , further comprising a sensitizer C, wherein the percentage of the sensitizer C relative to the ultraviolet curable resin composition is 0.05 mass % or more. 6 . The ultraviolet curable resin composition according to claim 1 , which is used for producing an optical component that transmits light emitted from a light source. 7 . The ultraviolet curable resin composition according to claim 1 , which is formed by an inkjet method. 8 . The ultraviolet curable resin composition according to claim 1 , wherein at least one of the viscosity at 25° C. and the viscosity at 40° C. is 30 mPa·s or less. 9 . An optical component comprising a cured product of the ultraviolet curable resin composition according to claim 1 .
10. A method for manufacturing an optical component, comprising: After the ultraviolet curable resin composition according to any one of claims 1 to 8 is molded by an inkjet method, the ultraviolet curable resin composition is irradiated with ultraviolet rays to be cured. 11 . A light emitting device comprising a light source and an optical component that transmits light emitted from the light source, wherein the optical component comprises a cured product of the ultraviolet curable resin composition according to claim 1 .
12. A method for manufacturing a light emitting device, comprising: manufacturing a light emitting device comprising a light source and an optical component for transmitting light emitted by the light source; The manufacturing method comprises the step of manufacturing the optical component by the method according to claim 10 .
Citation Information
Patent Citations
New o-acyloxime photopolymerization initiator
JP2000080068A
Photoinitiator of oxime ester
JP2001233842A
Oxime ester photopolymerization initiator
JP2010527338A
Oxime ester photopolymerization initiator
JP2010527339A
Photosensitive resin composition for photospacer and photospacer using the same
JP2013041153A